Adaptive Variation Amid High Gene Flow Across a Broad Latitudinal Gradient in the Reef‐Building Honeycomb Worm, Sabellaria alveolata - Edward J. Wilson; Antony M. Knights; Louise B. Firth; Charlotte Corporeau; Amelia Curd; Stanislas F. Dubois; Fernando P. Lima; Rui Seabra; Flavia L. D. Nunes (Molecular Ecology, 2026)
Climate change is already altering, and will continue to reshape, the persistence and spatial structure of marine populations. Understanding metapopulation connectivity and local adaptation is therefore critical for identifying both vulnerable populations and those with adaptive resilience. We applied a seascape genomics approach to investigate connectivity patterns and adaptive responses in the honeycomb worm, Sabellaria alveolata —an intertidal ecosystem engineer that supports high biodiversity and provides essential ecological functions. A total of 286 individuals from 17 sites spanning the entire latitudinal range were genotyped to assess population structure and local adaptation. Outlier analyses (BayeScan and OutFlank) identified six adaptive and 2117 neutral SNPs. Neutral SNP analysis revealed low to moderate genetic differentiation, indicating well‐connected populations. Admixture with possible ancestral gene pools in Southern Edge and Biscay populations suggests the persistence of unique genetic diversity. While connectivity is likely driven by natural larval dispersal, human‐mediated transport resulting from support vessels, aquaculture, marine debris and expanding offshore and coastal infrastructure may also facilitate gene flow, shaping observed genetic patterns. Despite this high connectivity, we detected genetic signatures of adaptation to temperature, salinity and net primary productivity, with adaptive SNPs linked to genes involved in molecular and physiological responses to these environmental factors. Our findings suggest that S. alveolata is likely resilient to climate change and other anthropogenic pressures, making it a valuable model for investigating the genetic and physiological underpinnings of marine population resilience.

Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

Processes affecting pollution fluxes during the coastal erosion of legacy colliery wastes - Ian T. Burke; Sebastian J. Pitman; James Hodson; Lin Niu; Fatmah Mohammed; Jenni Ilari Skakunova; Alex L. Riley; Catherine J. Gandy; Elliot Whitehead; Karen A. Hudson-Edwards; Elin Jennings; Helen Jay; et al. (Applied Geochemistry, 2026)

Regional oceanographic controls on water column nitrogen fixation in northern Australian waters - Douglas G. Capone; Ajit Subramaniam; Yubin Raut; Joseph P. Montoya; Margaret R. Mulholland; Rachel Ann Foster; Miles Furnas; Edward J. Carpenter (Frontiers in Marine Science, 2026)
Large blooms of the diazotrophic cyanobacteria, Trichodesmium , have been reported along the north coast of Australia and are readily evident in remote sensing images. During a research cruise in November 1999, we sampled from Townsville to Broome, examined Trichodesmium population densities and their rates of carbon and N 2 fixation alongside microscopy-based cell counts of them and other cyanobacterial diazotrophs. Additionally, we also enumerated the picophytoplankton community using flow-cytometry, measured bulk chlorophyll concentrations, carbon and N 2 fixation rates, and water column hydrography, enabling comparison of diazotrophic and picophytoplankton functional groups across the system. Agglomerative hierarchical clustering analysis of physicochemical oceanographic variables identified four distinct clusters that generally corresponded to the five geographic regions traversed and were supported by principal component analysis. In some cases, cluster analysis of physical parameters revealed close similarity of water masses in different, distal regions. High surface densities (up to 10,000 trichomes per L) and visible surface slicks of Trichodesmium were encountered at many of the stations where N 2 fixation could be directly measured in unconcentrated surface samples. Areal rates of N 2 fixation in excess of 1 mmol N m −2 d −1 were noted at several stations, with the highest average N 2 fixation rates found in the Timor Sea. Although spatial relationships between bulk phytoplankton biomass and carbon fixation rates versus contributions from Trichodesmium were complex, Trichodesmium contributed as much as 25% of total primary production and accounted for more than 50% of surface phytoplankton biomass in the Coral Sea. Lastly, Trichodesmium dominance was observed alongside diatom-diazotroph associations, the unicellular cyanobacteria Crocosphaera sp., and picophytoplankton assemblages, which collectively indicated that nitrogen fixation and primary production were partitioned among distinct phytoplankton and diazotrophic functional groups across hydrographic gradients.

Within day temperature variation and pediatric asthma exacerbation in Philadelphia, PA - Janelle R. Edwards; Anneclaire J. De Roos; Chén Kenyon; Irene Headen; Loni P. Tabb; Leah H. Schinasi (International Journal of Hygiene and Environmental Health, 2026)

Land sparing outperforms land sharing across an elevational gradient in tropical cattle-farming landscapes - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; James. J. Gilroy; David P. Edwards (Biological Conservation, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Promoting Research Excellence in Down Syndrome: Proceedings of the 5th International Conference of the Trisomy 21 Research Society - Fabio Di Domenico; Marzia Perluigi; Antonella Tramutola; Maria Giulia Bacalini; Daniella Balduino Victorino; Isabel Barroeta; Renata Bartesaghi; Angelo Carfi; Maria Carmona-Iragui; Ann D. Cohen; Alberto C. S. Costa; Floriana Costanzo; et al. (NeuroMolecular Medicine, 2026)
Down syndrome (DS), or trisomy 21 (T21), represents the most common genetic cause of intellectual disability worldwide and is associated with a wide range of medical, developmental, and neurodegenerative conditions, including a universal predisposition to early-onset Alzheimer’s disease (AD). Since its establishment in 2014, the Trisomy 21 Research Society (T21RS) has provided a global forum for advancing DS research across disciplines and promoting translational efforts to improve health and quality of life. Every two years, T21RS hosts an international scientific meeting that brings together researchers, clinicians, self-advocates, families, and industry stakeholders. In 2024, the 5th T21RS International Conference was held in Rome, Italy, from June 5 to 8, under the theme “Promoting Research Excellence in Down Syndrome.” The meeting brought together about 500 scientists from 26 countries across five continents, and more than 900 attendees overall, including families and caregivers. The scientific program featured 5 keynote lectures, 2 satellite meetings, 17 symposia, 7 nano symposia, 2 workshops, and 1 industry-focused session, totaling more than 150 oral presentations. More than 230 abstracts were presented as posters. The conference covered research across the lifespan of individuals with DS, spanning genomic and epigenetic regulation, molecular and cellular mechanisms, preclinical and experimental models, cognition and behavior, neurodevelopment, aging and neurodegeneration, co-occurring medical conditions, and therapeutic interventions. Dedicated sessions focused on capacity-building in DS research and societal engagement were established. Significantly, T21RS promoted inclusivity by supporting 60 young investigator fellowships, providing childcare awards, and organizing a two-day program for families and caregivers in collaboration with Italian DS associations. This proceeding summarizes the main scientific highlights of the 5th T21RS International Conference, reflecting the latest advances in DS biology, clinical research, biomarker development, and therapeutic innovation.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Observation of Rockfall in the Thermal Infrared - Edward C. Wellman; Kirk W. Schafer; Chad P. Williams; Greatness H. Ojum; Julia J. Potter; Leonard D. Brown; Benjamin Meyer; Bradley J. Ross; John Kemeny (Rock Mechanics and Rock Engineering, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Correction: Effects of Interphase and Interpulse Delays on Tissue Impedance and Pulsed Field Ablation - Edward J. Jacobs; Pedro P. Santos; Rafael V. Davalos (Annals of Biomedical Engineering, 2026)

Pathologic Description and Genetic Characterisation of Kudoa thunni From Yellowfin Tuna ( Thunnus albacares ) in the Caribbean Sea - Noor‐Ul Huda; Magali Duran; Jonnel Edwards; Cynthia Ware; Olando Harvey; Matt J. Griffin; David P. Marancik (Journal of Fish Diseases, 2026)
Yellowfin tuna ( Thunnus albacares ) is a valuable recreational and commercial species in Grenada and the Caribbean region. Myxozoans, specifically the monotypic Kudoidae family within the Order Multivalvulida, are marine parasitic organisms that can negatively impact fish health and marketability. On 8 September 2023, muscle fillets from a yellowfin tuna caught off the coast of Grenada and containing numerous white nodules were submitted for diagnostic evaluation. Gross examination of the muscle showed firm, spherical to ovoid, white polysporous cysts approx. 0.8–1.3 mm in diameter and approx. 10–20 cysts per 2 × 2 cm section of muscle. Cysts were sharply excised and assessed by wet mount cytology revealing a myriad of quadrate myxosporean parasites consistent with the genus Kudoa . Histopathologic examination demonstrated numerous, intracytoplasmic plasmodia with thick hyaline walls containing intact and necrotic myxospores. Parasites present outside of plasmodia were associated with myoliquifaction of the tissue. The case isolate was morphologically consistent with K. thunni and the partial 18S small subunit rDNA (SSU) and 28S large subunit rDNA (LSU) demonstrated high homology (SSU: 99.8%–100%; LSU: 99.5%–100%) to several K. thunni isolates, including those isolated from blackfin tuna ( T. atlanticus ) harvested near the Caribbean islands of St. Kitts and Nevis. This is the first report of K. thunni infecting yellowfin tuna in the Caribbean region and expands the epidemiologic, pathologic, and molecular record for this parasite.

Evaluation of siRNA-mediated knockdown of heat shock protein 16.2 in adult Acropora cervicornis - Edward P. Gniffke; Benjamin D. Young; Keir J. Macartney; Michael S. Studivan; Ian C. Enochs; Erin E. Easton (Frontiers in Marine Science, 2026)
Acropora cervicornis is a critically endangered Caribbean coral species facing a precipitous decline due to disease and thermal bleaching. To combat the loss of ecologically important reef-building corals, novel molecular approaches can be used to understand mechanisms of resilience and ultimately provide a means to modulate coral performance. In this study, we tested a recently developed method for gene knockdown in adult corals that utilizes short interfering RNAs (siRNAs) and the RNA interference pathway. The Heat Shock Protein 16.2 (HSP16.2) gene in fragments of adult A. cervicornis was targeted for knockdown using a single siRNA construct. RT-qPCR analysis of HSP16.2 gene expression was performed between filtered seawater, no template control siRNA (NTC), and siRNA targeting HSP16.2 across four genotypes of A. cervicornis with known differences in thermal susceptibility (two heat-tolerant and two heat-susceptible genotypes). There was no significant difference in HSP16.2 gene expression due to the treatment of HSP16.2 siRNAs versus controls, but we did identify a single genotype-driven effect that corroborates evidence that A. cervicornis heat tolerance is driven largely by genotype. No difference in photophysiological performance or mortality was observed between experimental and control treatments. There were, however, some differences in mortality and HSP16.2 expression among genotypes. Our results reveal that siRNA-mediated knockdown was not successful for this species and gene and thus further optimization is needed prior to broader applicability of siRNA-mediated knockdown in corals. We provide an assessment of potential methodological improvements to support the development of future reverse-genetics studies in corals.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The effects of tungsten inhalation and continuous administration of angiotensin II on cardiac injury and pulmonary outcomes - Milad MazloumiBakhshayesh; Russell P. Hunter; Brenna Baird; Rui Liu; Anahi Gabriela Jimenez-Campos; Siem Goitom; Edward B. Barr; Guy W. Herbert; Selita N. Lucas; Charlotte M. McVeigh; Jorge Moreno; Yiliang Zhu; et al. (Toxicology and Applied Pharmacology, 2026)

Beyond the Guinea Pig Myth: Understanding Complex Attitudes Toward Clinical Trials Participation in a Community Clinic - J. Edward Murrell; Ashleigh Allgood; Arya Tamhane; Regan Gaskin; Luis F. Pineda; Barry P. Sleckman; Raegan W. Durant; Soumya J. Niranjan (Journal of Cancer Education, 2026)

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

A Conceptual Framework and Methods for Studying the Connectivity of Fishes - Jordanna N. Bergman; Jessica A. Robichaud; Jasper McCutcheon; Michael T. Booth; Brendan Campbell; Grace A. Casselberry; Cienna R. Cooper; Bronwyn M. Gillanders; Lucas P. Griffin; Edward Hale; Luc LaRochelle; Karen J. Murchie; et al. (Fish and Fisheries, 2026)
Connectivity is a multifaceted concept that has important implications for the management and conservation of marine and freshwater fishes. We developed a conceptual framework that encompasses multiple, interrelated categories of connectedness, including landscape (e.g., structural, functional) connectivity and ecological (e.g., trophic, genetic, demographic) connectivity, that together shape the flow of organisms, energy and information across ecosystems. We also synthesised six key methods that can be used to study connectivity of fishes: (1) telemetry, including satellite, acoustic, radio and passive integrated transponders (PIT), (2) mark‐recapture, (3) environmental tracers, including stable isotopes and otolith‐microchemistry, (4) genetics, (5) community structure analysis and (6) emerging technologies and tools (e.g., remote sensing and artificial intelligence). For each method, we describe the categories of connectivity it can assess and provide real‐world examples where they have been effectively used. We also identify limitations of each method. This article highlights the diverse and evolving toolbox of methods used to assess fish connectivity, underscoring the need for continued collaboration, innovation and integration of new approaches to refine our understanding and address remaining challenges in this critical area of aquatic ecology and fisheries management.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Elevated organic carbon in African Dark Earths is not exclusively attributable to pyrogenic organic matter - Maura P. Slocum; Riley B. Barton; Sasha J. Wagner; Johannes Lehmann; Dawit Solomon; Edward Yeboah; Alain F. Plante (Science of The Total Environment, 2026)

Uncovering UK coastal legacy wastes and their potential contaminant release risks through mineralogy and geochemistry - Patrizia Onnis; Elin Jennings; Violeta Ramos; Alex L. Riley; Catherine J. Gandy; Rich A. Crane; Ian T. Burke; Gavyn K. Rollinson; Patrick Byrne; Bryan M. Spears; Justyna P. Olszewska; Will M. Mayes; et al. (Journal of Hazardous Materials, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Acute nutritional ketosis during early recovery from aerobic exercise does not affect skeletal muscle transcriptomic response in humans - Erick Mosquera-Lopez; Julien Louis; Jason P. Edwards; Jamie Pugh; Mark R. Viggars; Daniel J. Owens; Jose L. Areta (European Journal of Applied Physiology, 2026)
Purpose Nutritional ketosis is purported to enhance skeletal muscle recovery and adaptation to exercise, yet precise adaptive mechanisms are unknown. We investigated the post-exercise molecular response to ketone monoesters (KME) in skeletal muscle by characterising the early transcriptomic response. Methods Following a randomised, double-blind, crossover design, recreationally active men (n = 9, age: 26 ± 5 (means ± SD) y; V̇O 2max : 47 ± 4 mL·kg −1 ·min −1 ) completed two experimental trials where they ingested either 1.25 g·kg −1 of KME or a taste-matched placebo (PLA) drink during exercise (90-min cycling at 60% of V̇O 2max ) and 3-h recovery. Blood samples were taken throughout for hormone and metabolite analyses, and muscle biopsies were taken at baseline and 3 h post-exercise for glycogen and genome-wide gene expression analyses. Results Recovery ßHB concentrations were higher in KME (4.1 ± 0.7 mM) vs PLA (0.1 ± 0.0 mM, P < 0.001). Erythropoietin (EPO) showed a main effect of time ( P = 0.044), but no condition effect ( P = 0.087) or interaction ( P = 0.318). Skeletal muscle glycogen decreased post-exercise (−57%, P < 0.001) as expected, but showed no condition effect ( P = 0.889) or interaction ( P = 0.907). We measured the expression of 16,898 genes, and despite a clear time effect on the skeletal muscle transcriptome (1561 differentially expressed genes post vs pre-exercise; q < 0.05 fold change > ± 1.5), there was no effect of condition. Conclusions KME did not demonstrate an effect on EPO concentration, muscle glycogen or transcriptome, suggesting DNA translation is likely not a process directly regulated by acute ketonaemia that increases early post-exercise.

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Strong Variation in Land‐Use Change Impacts on Tropical Avian Phylogenetic Diversity Between Ecoregions Highlights the Need to Sample Large Spatial Scales - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Robert P. Freckleton; Torbjørn Haugaasen; James J. Gilroy; David P. Edwards (Global Change Biology, 2026)
Forest conversion for agriculture is a major cause of tropical biodiversity loss, but its impacts vary with spatial scale. Higher species turnover in forests than in farmland means that land‐use change causes greater biodiversity loss at broader than at local scales, yet broad‐scale assessments are scarce. Phylogenetic diversity is increasingly prioritised in conservation to protect evolutionary history under global change, yet how deforestation‐driven changes in phylogenetic diversity scale spatially and accumulate in regions of high species turnover remains unclear. We compiled a large field database from across 13 biogeographically diverse regions affected by deforestation for cattle farming, covering most of Colombia, a megadiverse tropical country. Using occupancy models, we estimated bird communities for 1547 (936 observed plus 611 never‐observed) species across ecoregions and nationally in both forest and pasture habitats to quantify changes in phylogenetic diversity metrics and determine whether these impacts are dependent on spatial scale. We found an average loss of 2300 Myr of phylogenetic diversity at the country scale, with most species negatively affected across the phylogeny. Although single regional‐scale relative loss was on average comparable to broader scales, there was high variability between regional units. The latter was especially critical when evaluating metrics of evolutionary distinctiveness, which are key indicators for biodiversity conservation planning. Such underestimation of national‐scale impacts highlights the importance of sampling across multiple regions. Immediate conservation action is needed to safeguard evolutionarily unique species and prevent phylogenetic homogenisation driven by agricultural expansion across spatial scales—a threat often underestimated due to assessments limited to single biogeographic regions.

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

High yield stability and susceptibility to stripe rust associate with large yield gaps in rainfed winter wheat - Nicolas Giordano; Victor O. Sadras; Mary J. Guttieri; Trevor J. Hefley; Jorge A. Romero Soler; Clark Neely; Jeffrey T. Edwards; Amanda de Oliveira Silva; Allan K. Fritz; Romulo P. Lollato (Field Crops Research, 2025)

Speciation and leaching behaviour of inorganic contaminants in actively eroding historical coastal municipal solid waste landfills - Ian T. Burke; Patrizia Onnis; Alex L. Riley; Catherine J. Gandy; Violeta Ramos; Gavyn K. Rollinson; Patrick Byrne; Richard A. Crane; Karen A. Hudson-Edwards; Elin Jennings; William M. Mayes; J. Frederick W. Mosselmans; et al. (Marine Pollution Bulletin, 2025)

Analysis of host and gut microbial biotransformation products of kratom (Mitragyna speciosa) by mass spectrometry - William J. Crandall; Ken H. Liu; Choon M. Lee; Grant Singer; Jaclyn Weinberg; Edward T. Morgan; Dean P. Jones; Cassandra L. Quave (Phytochemistry Letters, 2025)

Hidden Nutrient Gaps: The Association Between Healthy Eating index-2020 Scores and Micronutrient Gaps - C. Edwards; J. Townsend; P. Sapp; T. Kirby; L. Nyman; R. Esposito (Journal of the Academy of Nutrition and Dietetics, 2025)

AG1® Supplementation Improves Gut Microbiome Composition and Relative Abundance of Growth/Nutrient Metabolism Gene Pathways in Adults with Occasional Gastrointestinal Issues - T. Kirby; J. Townsend; P. Sapp; C. Edwards; J. Wright; R. Lamendella; L. Nyman; R. Esposito (Journal of the Academy of Nutrition and Dietetics, 2025)

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

Dynamic of infectious aerosols generated by cough from patients with pulmonary tuberculosis - Taline Canto Tristão; Mariana Abou Mourad Ferreira; Pedro Sousa de Almeida Júnior; Luiz Guilherme Schmidt Castellani; Manuela Negrelli Brunetti; Edward C. Jones-López; Kevin P. Fennelly; Michael R. Barer; Carlos Henrique Fantecelle; Saulo Almeida Morellato; David Jamil Hadad; Jerrold J. Ellner; et al. (Journal of Aerosol Science, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Effects of Interphase and Interpulse Delays on Tissue Impedance and Pulsed Field Ablation - Edward J. Jacobs; Pedro P. Santos; Rafael V. Davalos (Annals of Biomedical Engineering, 2025)
Purpose High-frequency irreversible electroporation (H-FIRE) is a pulsed field ablation (PFA) technique that employs a series of high-voltage, microseconds-long positive and negative pulses, separated by interphase (d1) and interpulse (d2) delays to non-thermally ablate tissue. Previous experimental and computational data suggest an impact of delays on nerve excitation and electrochemical effects. However, the impact of delays on PFA outcomes, such as change in resistance and ablation generation, has only recently started to be elucidated. Methods While recording the applied voltage and currents, we delivered a series of increasing voltages, termed voltage ramps, into tuber and cardiac tissues using both needle electrode pairs and flat plate electrodes. Tissues were stained for metabolic activity to measure irreversible electroporation areas following treatment. Results Our findings support previous in vitro data that delays do not significantly affect ablation areas. While there were significant differences in applied current, resistance, and conductivity between different pulse widths at sub-electroporation electric fields, we found no significant differences after inducing electroporation between different delays and pulse widths. Consequently, since delays do not affect ablation areas or local conductivity, the data suggests that delays should not affect the electric field threshold or Joule heating within the tissue. Conclusion The findings presented here provide critical insights into electroporation-dependent tissue conductivity changes from H-FIRE with implications for improving H-FIRE parameterization and computational models for treatment planning in cancer and cardiac pulsed field ablation.

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Selection of suitable reference gene for gene expression studies in maize-downy mildew pathosystem - Benjamine William P. Cordez; Edward Cedrick J. Fernandez; Jen Daine L. Nocum; Fe M. Dela Cueva; Anand Noel C. Manohar; Darlon V. Lantican (Physiological and Molecular Plant Pathology, 2025)

A dynamic meshing scheme for integrated hydrologic modeling to represent evolving landscapes - Hyoun-Tae Hwang; Young-Jin Park; Steven J. Berg; Jon P. Jones; Killian L. Miller; Edward A. Sudicky (Science of The Total Environment, 2025)

Interfacial electromigration for accelerated reactions - Madison E. Edwards; Annesha Sengupta; Dallas P. Freitas; Erin A. Hirtzel; Xi Chen; Joohan J. Kim; Xin Yan (Analytica Chimica Acta, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Photodynamic priming with red light triggers adaptive immune responses in a pancreatic cancer mouse model - Pushpamali De Silva; Mohammad A. Saad; Joseph W.R. Swain; Zhiming Mai; Madeline D. Kidd; Joanna J. Choe; Assiris P. Camargo; Sanjay Anand; Vinay Chandrasekhara; Brian W. Pogue; Kenneth K. Wang; Bryan Q. Spring; et al. (Journal of Photochemistry and Photobiology B: Biology, 2025)

John Raven, FRS, FRSE: a truly great innovator in plant physiology, photosynthesis and much more - A. W. D. Larkum; P. G. Falkowski; Dianne Edwards; C. B. Osmond; H. Lambers; P. Sanchez-Baracaldo; R. J. Ritchie; J. W. Runcie; P. J. Ralph; M. Westoby; S. Maberly; H. Griffiths; et al. (Photosynthesis Research, 2025)
This is a tribute to a truly inspirational plant biologist, Prof. John A. Raven, FRS, FRSE (25th June 1941– 23rd May 2024), who died at the age of 82. He was a leader in the field of evolution and physiology of algae and land plants. His research touched on many areas including photosynthesis, ion transport, carbon utilisation, mineral use, such as silicon, iron and molybdenum, the evolution of phytoplankton, the evolution of root systems, the impact of global change, especially on the acidification of the oceans, carbon gain and water use in early land plants, and ways of detecting extraterrestrial photosynthesis. Beginning his research career in the Botany School, University of Cambridge, John studied ion uptake in a giant algal cell. This was at the time of great strides brought about by Peter Mitchell (1920–1992) in elucidating the role of energy generation in mitochondria and chloroplasts and the coupling of ion transport systems to energy generation. With Enid MacRobbie and Andrew Smith, John pioneered early work on the involvement of ion transport in the growth and metabolism of plant cells.On leaving Cambridge John took up a lectureship at the University of Dundee in 1971, where he was still attached upon his death. His primary focus over the years, with one of us (Paul Falkowski), was on phytoplankton, the photosynthetic microalgae of the oceans. Still, his publication list of 5 books and over 600 scientific papers spans a very broad range. The many highly cited papers (see Table 1) attest to an outstanding innovator, who influenced a multitude of students and coworkers and a very wide readership worldwide. At the personal level, John Raven was a wonderful human being; he had an extraordinary memory, dredging up facts and little-known scientific papers, like a scientific magician, but at the same time making humorous jokes and involving his colleagues in fun and sympathetic appreciation. Table 1 Ten best cited articles (from google scholar) Citations Date Aquatic Photosynthesis, 3rd EditionP.G. Falkowski & J.A. RavenPrinceton University Press, 2013 3854 2013 The evolution of modern eukaryotic phytoplanktonP.G. Falkowski, M.E. Katz, A.H. Knoll, A. Quigg, J.A. Raven, et alScience 305 , 354–360 1790 2004 C O 2 concentrating mechanisms in algae:mechanisms, environmental modulation, and evolutionM. Giordano, J. Beardall & J.A. RavenAnnu. Rev. Plant Biol. 56 (1), 99–131 1648 2005 Algae as nutritional food sources: revisiting our understandingM.L. Wells, P. Potin, J.S. Craigie, J.A. Raven, S.S. Merchant, et alJournal of applied phycology 29 , 949–982 1527 2017 Plant Nutrient acquisition strategies change with soil ageH. Lambers, J.A. Raven, G.R. Shaver & S.E. SmithTrends in ecology & evolution 23 , 95–103 1488 2008 Ocean acidification due to increasing atmospheric carbon dioxideJ. Raven, K. Caldeira, H. Elderfield, O. Hoegh-Guldberg, P. Liss, et alThe Royal Society, Policy Document, June 2005 1470 2005 Phytoplankton in a changing world: cell size and elemental stoichiometryZ.V. Finkel, J. Beardall, K.J. Flynn, A. Quigg, T.A.V. Rees & J.A. RavenJournal of plankton research 32 , 119–137 1198 2010 Opportunities for improving phosphorus efficiency in crop plantsE.J. Veneklaas, H. Lambers, J. Bragg, P.M. Finnegan, C.E. Lovelock, et alNew phytologist 195 , 306–320 951 2012 Adaptation of unicellular algae to irradiance: an analysis of strategiesK. Richardson, J. Beardall & J.A. RavenNew Phytologist 93 , 157–191 914 1983 N itrogen assimilation and transport in vascular land plants in relation to Intracellular pH regulationJ.A. Raven & F.A. SmithNew Phytologist 76 , 415–431 893 1976 Temperature and algal growth J.A. Raven & R.J. GeiderNew phytologist 110 , 441–461 867 1988 The role of trace metals in photosynthetic electron transport in O 2 -evolving organismsJ.A. Raven, M.C.W. Evans & R.E. KorbPhotosynthesis Research 60 , 111–150 840 1999

Correction: Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales‑Garcia; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz‑Chavez; Ivan T. Ahumada‑Carrillo; Ricardo Ramirez‑Chaparro; Miguel Angel de la Torre‑Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2025)

Non-serous ovarian cancer in PTEN Hamartoma Tumor Syndrome: additional evidence for increased risk - Ane J. Schei-Andersen; Vera M. Witjes; Janet R. Vos; Arjen R. Mensenkamp; Anne van Altena; Jolanda Schieving; Michiel Simons; Janneke H. M. Schuurs-Hoeijmakers; Muriel A. Adank; Liselotte P. van Hest; Yvette van Ierland; Mirjam de Jong; et al. (Familial Cancer, 2025)
Increased hereditary cancer risk is one of the hallmarks of PTEN Hamartoma Tumor Syndrome (PHTS) which is caused by a pathogenic germline variant in PTEN . Case reports and some cohort studies have described ovarian cancer (OC) in PHTS patients. Previously, we observed an enrichment of non-serous OC in PHTS compared to sporadic cases (3% vs 1%). However, ovarian cancer is currently not considered a PHTS-related cancer. The aim of this study was to describe five PHTS patients with a pathogenic germline variant in PTEN with non-serous OC. Three of the non-serous OCs were mucinous carcinomas (49, 51 and 52 years) and two were malignant germ cell tumors (8 and 15 years) and all were diagnosed before genetic testing and PHTS diagnosis. In addition to OC, the described patients developed other PHTS-related benign and malignant lesions. We provide further evidence that non-serous ovarian cancer, especially mucinous, endometrioid and malignant germ cell tumors should be further investigated as potential PHTS-related cancers.

Spatial variability of metal(loid) leaching from coastal colliery wastes under freshwater and saline water conditions - Catherine J. Gandy; Ian T. Burke; Patrick Byrne; Nick Cooper; Richard A. Crane; Karen A. Hudson-Edwards; William M. Mayes; Patrizia Onnis; Alex L. Riley; Adam P. Jarvis (Journal of Environmental Management, 2025)

Comparative Transcriptomics Reveals the Molecular Mechanisms of Maize in Response to Downy Mildew Disease Caused by Peronosclerospora philippinensis (Weston) Shaw - Edward Cedrick J. Fernandez; Eliza Vie M. Simon-Ada; Jay-Vee S. Mendoza; Anand Noel C. Manohar; Roanne R. Gardoce; Tonette P. Laude; Fe M. Dela Cueva; Darlon V. Lantican (Plant Molecular Biology Reporter, 2025)

Synthesis of encapsulated nanofertilizer from biogas plant digestate - Edward D. Nasser; Joel Kenneth M. Ngojo; Ramiro Emerson C. Amon; Jayvee Moore S. Dy; Julius J. Rosalia; Chosel P. Lawagon (Bioresource Technology Reports, 2025)

Ecosystem Changes Caused by Hydrological Change are Associated with Population Decline in a Formerly-Common Grazing Herbivore - W. J. Blaser-Hart; G. K. Shanungu; P. J. Edwards; J. Harms; S. P. H. Hart; G. A. Ellenbroek; H. A. M. J. van Gils; C. Simukonda; H. Olde Venterink (Ecosystems, 2025)
Few ecosystems are more sensitive to hydrological change than seasonally-flooded wetlands. Here, we investigate how changes in hydrological regimes caused by the construction of two dams have contributed to large changes in the structure and dynamics of the Kafue Flats, an internationally-important, partially-protected wetland ecosystem in Zambia. We use historical (1970) and contemporary (2013) data to describe changes in hydrology due to dam operations, and to compare the areal extent, distribution, and composition of the major wetland and dryland habitats in the pre- and post-dam periods. To understand the seasonal dynamics of the ecosystem and how these dynamics influence the seasonal movement and use of the ecosystem by the dominant grazing herbivore, the endangered Kafue lechwe, we combine data on annual hydrological variation with spatially- and/or temporally-explicit quantitative estimates of: (1) grass biomass and nutrient stocks, (2) distribution of lechwe across habitats, and (3) lechwe nutritional status. The operation of the dams has reduced hydrological variation, causing a loss of more than 50% of seasonally-flooded grasslands and probably promoting woody encroachment in some habitats. Our results demonstrate that Kafue lechwe is highly dependent on these seasonally-flooded grasslands during the dry season, when their nutritional status is otherwise critically low. In combination, we hypothesize that changes in the flooding regime driven by dam construction precipitated ecosystem-level changes that—together with other factors—may have contributed to a rapid historic, as well as ongoing decline in the lechwe population. Our study highlights potential consequences of the spatio-temporal homogenization of a previously highly variable ecosystem.

The need for carbon finance schemes to tackle overexploitation of tropical forest wildlife - Caroline E. Milson; Jun Ying Lim; Daniel J. Ingram; David P. Edwards (Conservation Biology, 2025)
Defaunation of tropical forests, particularly from unsustainable hunting, has diminished populations of key seed dispersers for many tree species, driving shifts in forest community composition toward small‐fruited or wind‐dispersed trees with low wood density. Such shifts can reduce aboveground biomass, prompting calls for overexploitation to be included in bioeconomic policy, but a synthesis of existing literature for wildlife impacts on carbon stores is lacking. We evaluated the role of wildlife in tropical forest tree recruitment and found that it was critical to tropical forest carbon dynamics. The emerging financial value of ecosystem services provided by tropical forest fauna highlights the need for carbon‐based payments for ecosystem services schemes to include wildlife protection. We argue for three cost‐effective actions within carbon finance schemes that can facilitate wildlife protection: support land security opportunities for Indigenous peoples and local communities; provide support for local people to protect forest fauna from overexploitation; and focus on natural regeneration in restoration projects. Incorporating defaunation in carbon‐financing schemes more broadly requires an increased duration of carbon projects and an improved understanding of defaunation impacts on carbon stores and ecosystem‐level models. Without urgent action to halt wildlife losses and prevent empty forest syndrome, the crucial role of tropical forests in tackling climate change may be in jeopardy.

Canopy complexity drives positive effects of tree diversity on productivity in two tree diversity experiments - Catherine Fahey; Dennis Choi; Jianmin Wang; Grant M. Domke; Joseph D. Edwards; Songlin Fei; Stephanie N. Kivlin; Elizabeth A. LaRue; Melissa K. McCormick; William J. McShea; Richard P. Phillips; Jamie Pullen; et al. (Ecology, 2025)
Forest canopy complexity (i.e., the three‐dimensional structure of the canopy) is often associated with increased species diversity as well as high primary productivity across natural forests. However, canopy complexity, tree diversity, and productivity are often confounded in natural forests, and the mechanisms of these relationships remain unclear. Here, we used two large tree diversity experiments in North America to assess three hypotheses: (1) increasing tree diversity leads to increased canopy complexity, (2) canopy complexity is positively related to tree productivity, and (3) the relationship between tree diversity and tree productivity is indirect and driven by the positive effects of canopy complexity. We found that increasing tree diversity from monocultures to mixtures of 12 species increases canopy complexity and productivity by up to 71% and 73%, respectively. Moreover, structural equation modeling indicates that the effects of tree diversity on productivity are indirect and mediated primarily by changes in internal canopy complexity. Ultimately, we suggest that increasing canopy complexity can be a major mechanism by which tree diversity enhances productivity in young forests.

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Impact of endophyte-infected tall fescue seed consumption on endocrine changes associated with intake regulation and post-absorptive metabolism in growing steers - Mindy E. King; Hannah M. Herzing; Kyle R. McLeod; James L. Klotz; Andrew P. Foote; J. Lannett Edwards; David L. Harmon (Domestic Animal Endocrinology, 2024)

Optimizing photosynthetic light-harvesting under stars: simple and general antenna models - Samir Chitnavis; Callum Gray; Ifigeneia Rousouli; Edward Gillen; Conrad W. Mullineaux; Thomas J. Haworth; Christopher D. P. Duffy (Photosynthesis Research, 2024)
In the next 10–20 years, several observatories will aim to detect the signatures of oxygenic photosynthesis on exoplanets, though targets must be carefully selected. Most known potentially habitable exo-planets orbit cool M-dwarf stars, which have limited emission in the photosynthetically active region of the spectrum (PAR, $$400< λ < 700$$ 400 < λ < 700 nm) used by Earth’s oxygenic photoautotrophs. Still, recent experiments have shown that model cyanobacteria, algae, and non-vascular plants grow comfortably under simulated M-dwarf light, though vascular plants struggle. Here, we hypothesize that this is partly due to the different ways they harvest light, reflecting some general rule that determines how photosynthetic antenna structures may evolve under different stars. We construct a simple thermodynamic model of an oxygenic antenna-reaction centre supercomplex and determine the optimum structure, size and absorption spectrum under light from several star types. For the hotter G (e.g. the Sun) and K-stars, a small modular antenna is optimal and qualitatively resembles the PSII-LHCII supercomplex of higher plants. For the cooler M-dwarfs, a very large antenna with a steep ’energy funnel’ is required, resembling the cyanobacterial phycobilisome. For the coolest M-dwarfs an upper limit is reached, where increasing antenna size further is subject to steep diminishing returns in photosynthetic output. We conclude that G- and K-stars could support a range of niches for oxygenic photo-autotrophs, including high-light adapted canopy vegetation that may generate detectable bio-signatures. M-dwarfs may only be able to support low light-adapted organisms that have to invest considerable resources in maintaining a large antenna. This may negatively impact global coverage and therefore detectability.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Meals for the dead: investigating Romano-British accessory vessels in burials using organic residue analysis - Julie Dunne; Edward Biddulph; Lucy J. E. Cramp; Caitlin Greenwood; Enid Allison; Jeremy Evans; Richard Helm; Bekky Hillman; Malcolm Lyne; Nigel Page; Caroline Rann; Richard P. Evershed (Archaeological and Anthropological Sciences, 2024)
Accessory vessels, including platters, dishes, beakers, flagons, jars, and amphorae, are a common feature of Romano-British burials, raising questions as to their provenance; for example, were such vessels recycled from the domestic sphere or made specially for funerary purposes? Furthermore, uncertainty surrounds their purpose: did they contain foods for the deceased, possibly for their final journey to the underworld? Interestingly, organic residue analysis of vessels from Baginton, a site adjacent to The Lunt fort, Coventry, an early (mid to late first century) Roman military cremation cemetery did not yield evidence for food offerings and may have reflected the use of seconds or damaged vessels in burials, perhaps to provide a symbolic meal. In contrast, here we provide, for the first time, direct chemical and isotopic evidence for ‘meals for the dead’, comprising mainly dairy products, often mixed with leafy plants, extracted from somewhat unusual accessory vessels found in a small, enclosed inhumation cemetery, perhaps associated with a family group, which dates to the late (third to late fourth century, or early fifth century A.D) in urban Canterbury. Thus, we can confirm that accessory vessels found in later Romano-British burials were, in this instance, used in the laying out of funerary meals, presumably to nourish the soul on the journey to the underworld. These preliminary insights on vessel use and burial practices across the span of the Roman occupation of Britain thus provide a strong hint at the diversity of Roman burial practices.

Resistance response of yellow maize inbreds and F1 crosses against Philippine downy mildew [Peronosclerospora philippinensis (Weston) C.G. Shaw] - Eliza Vie M. Simon-Ada; Jay-Vee S. Mendoza; Edward Cedrick J. Fernandez; John Paolo P. Nuñez; Fe M. Dela Cueva; Anand Noel C. Manohar; Roanne R. Gardoce; Tonette P. Laude; Darlon V. Lantican (Crop Protection, 2024)

TTCF4LAMMPS: A toolkit for simulation of the non-equilibrium behaviour of molecular fluids at experimentally accessible shear rates - Luca Maffioli; James P. Ewen; Edward R. Smith; Sleeba Varghese; Peter J. Daivis; Daniele Dini; B.D. Todd (Computer Physics Communications, 2024)

Environmental behaviour of iron and steel slags in coastal settings - Alex L. Riley; James Cameron; Ian T. Burke; Patrizia Onnis; John M. MacDonald; Catherine J. Gandy; Richard A. Crane; Patrick Byrne; Sean Comber; Adam P. Jarvis; Karen A. Hudson-Edwards; William M. Mayes (Environmental Science and Pollution Research, 2024)
Iron and steel slags have a long history of both disposal and beneficial use in the coastal zone. Despite the large volumes of slag deposited, comprehensive assessments of potential risks associated with metal(loid) leaching from iron and steel by-products are rare for coastal systems. This study provides a national-scale overview of the 14 known slag deposits in the coastal environment of Great Britain (those within 100 m of the mean high-water mark), comprising geochemical characterisation and leaching test data (using both low and high ionic strength waters) to assess potential leaching risks. The seaward facing length of slag deposits totalled at least 76 km, and are predominantly composed of blast furnace (iron-making) slags from the early to mid-20th Century. Some of these form tidal barriers and formal coastal defence structures, but larger deposits are associated with historical coastal disposal in many former areas of iron and steel production, notably the Cumbrian coast of England. Slag deposits are dominated by melilite phases (e.g. gehlenite), with evidence of secondary mineral formation (e.g. gypsum, calcite) indicative of weathering. Leaching tests typically show lower element (e.g. Ba, V, Cr, Fe) release under seawater leaching scenarios compared to deionised water, largely ascribable to the pH buffering provided by the former. Only Mn and Mo showed elevated leaching concentrations in seawater treatments, though at modest levels (<3 mg/L and 0.01 mg/L, respectively). No significant leaching of potentially ecotoxic elements such as Cr and V (mean leachate concentrations <0.006 mg/L for both) were apparent in seawater, which micro-X-Ray Absorption Near Edge Structure (μXANES) analysis show are both present in slags in low valence (and low toxicity) forms. Although there may be physical hazards posed by extensive erosion of deposits in high-energy coastlines, the data suggest seawater leaching of coastal iron and steel slags in the UK is likely to pose minimal environmental risk.

Photogrammetry scans for neuroanatomy education - a new multi-camera system: technical note - André S. B. Oliveira; Luciano C. P. C. Leonel; Megan M. J. Bauman; Alessandro De Bonis; Edward R. LaHood; Stephen Graepel; Michael J. Link; Carlos D. Pinheiro-Neto; Nirusha Lachman; Jonathan M. Morris; Maria Peris-Celda (Neuroinformatics, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Quantification of age-related changes in the structure and mechanical function of skin with multiscale imaging - Alan E. Woessner; Nathan J. Witt; Jake D. Jones; Edward A. Sander; Kyle P. Quinn (GeroScience, 2024)
The mechanical properties of skin change during aging but the relationships between structure and mechanical function remain poorly understood. Previous work has shown that young skin exhibits a substantial decrease in tissue volume, a large macro-scale Poisson’s ratio, and an increase in micro-scale collagen fiber alignment during mechanical stretch. In this study, label-free multiphoton microscopy was used to quantify how the microstructure and fiber kinematics of aged mouse skin affect its mechanical function. In an unloaded state, aged skin was found to have less collagen alignment and more non-enzymatic collagen fiber crosslinks. Skin samples were then loaded in uniaxial tension and aged skin exhibited a lower mechanical stiffness compared to young skin. Aged tissue also demonstrated less volume reduction and a lower macro-scale Poisson’s ratio at 10% uniaxial strain, but not at 20% strain. The magnitude of 3D fiber realignment in the direction of loading was not different between age groups, and the amount of realignment in young and aged skin was less than expected based on theoretical fiber kinematics affine to the local deformation. These findings provide key insights on how the collagen fiber microstructure changes with age, and how those changes affect the mechanical function of skin, findings which may help guide wound healing or anti-aging treatments.

Long- and short-term soil storage methods other than freezing can be useful for DNA-based microbial community analysis - Joseph D. Edwards; Sarah J. Love; Richard P. Phillips; Songlin Fei; Grant Domke; John D. Parker; Melissa McCormick; Elizabeth A. LaRue; Jennifer A. Schweitzer; Joseph K. Bailey; James Fordyce; Stephanie N. Kivlin (Soil Biology and Biochemistry, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Host and geography impact virus diversity in New Zealand’s longfin and shortfin eels - Stephanie J. Waller; Eimear Egan; Shannan Crow; Anthony Charsley; P. Mark Lokman; Erica K. Williams; Edward C. Holmes; Jemma L. Geoghegan (Archives of Virology, 2024)
The fishing and aquaculture industry is vital for global food security, yet viral diseases can result in mass fish die-off events. Determining the viromes of traditionally understudied species, such as fish, enhances our understanding of the global virosphere and the factors that influence virome composition and disease emergence. Very little is known about the viruses present in New Zealand’s native fish species, including the shortfin eel ( Anguilla australis ) and the longfin eel ( Anguilla dieffenbachii ), both of which are fished culturally by Māori (the indigenous population of New Zealand) and commercially. Through a total RNA metatranscriptomic analysis of longfin and shortfin eels across three different geographic locations in the South Island of New Zealand, we aimed to determine whether viruses had jumped between the two eel species and whether eel virome composition was impacted by life stage, species, and geographic location. We identified nine viral species spanning eight different families, thereby enhancing our understanding of eel virus diversity in New Zealand and the host range of these viral families. Viruses of the family Flaviviridae (genus Hepacivirus ) were widespread and found in both longfin and shortfin eels, indicative of cross-species transmission or virus-host co-divergence. Notably, both host specificity and geographic location appeared to influence eel virome composition, highlighting the complex interaction between viruses, hosts, and their ecosystems. This study broadens our understanding of viromes in aquatic hosts and highlights the importance of gaining baseline knowledge of fish viral abundance and diversity, particularly in aquatic species that are facing population declines.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

Planktonic habitats in the Amazon Plume region of the Western Tropical North Atlantic - Anh H. Pham; Noémie Choisnard; Ana Fernández-Carrera; Ajit Subramaniam; Erica K. Strope; Edward J. Carpenter; Maren Voss; Joseph P. Montoya (Frontiers in Marine Science, 2024)
The Western Tropical North Atlantic is a highly dynamic marine system where the Amazon River Plume (ARP) generates a patchwork of environmental conditions that favor different phytoplankton groups. To study phytoplanktonic community structure in such heterogeneous conditions, we used a set of five standard ship-based measurements taken from oceanographic surveys between 2010 and 2021 to characterize different habitat types. We then utilized a variety of multiparametric approaches to examine phytoplankton biodiversity in the different habitats to assess the biological relevance of our delineated habitats. Our approach generated a consistent set of habitat types across cruises carried out in multiple different years and the Amazon’s two predominant (wet and dry) seasons. Our phytoplankton community analyses revealed strong distinctions among all habitats along the plume gradient using in-vivo fluorescence and diagnostic pigments, and clear contrasts of diazotroph community along the mesohaline waters using direct cell-count, a pattern consistent with niche partitioning among similar species. The few apparent mismatches we found between phytoplankton community composition and habitat may reflect recent hydrographic changes driven by mixing and/or upwelling and thus may be a useful index to biologically-relevant temporal variation. Our habitat classification approach is straightforward and broadly applicable in identifying biologically distinct areas within heterogeneous and dynamic regions of the ocean.

Multi-fidelity data-adaptive autonomous seakeeping - Michael D. Levine; Samuel J. Edwards; Dayne Howard; Kenneth Weems; Themistoklis P. Sapsis; Vladas Pipiras (Ocean Engineering, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Low frequency of resistance to thiophanate-methyl in Monilinia fructicola populations from southeastern United States peach orchards - William P. Gura; Jhulia Gelain; Edward J. Sikora; Edgar L. Vinson; Phillip M. Brannen; Guido Schnabel (Pesticide Biochemistry and Physiology, 2023)

Modulating signalling lifetime to optimise a prototypical animal opsin for optogenetic applications - Jessica Rodgers; Phillip Wright; Edward R. Ballister; Rebecca B. Hughes; Riccardo Storchi; Jonathan Wynne; Franck P. Martial; Robert J. Lucas (Pflügers Archiv - European Journal of Physiology, 2023)
Animal opsins are light activated G-protein-coupled receptors, capable of optogenetic control of G-protein signalling for research or therapeutic applications. Animal opsins offer excellent photosensitivity, but their temporal resolution can be limited by long photoresponse duration when expressed outside their native cellular environment. Here, we explore methods for addressing this limitation for a prototypical animal opsin (human rod opsin) in HEK293T cells. We find that the application of the canonical rhodopsin kinase (GRK1)/visual arrestin signal termination mechanism to this problem is complicated by a generalised suppressive effect of GRK1 expression. This attenuation can be overcome using phosphorylation-independent mutants of arrestin, especially when these are tethered to the opsin protein. We further show that point mutations targeting the Schiff base stability of the opsin can also reduce signalling lifetime. Finally, we apply one such mutation (E122Q) to improve the temporal fidelity of restored visual responses following ectopic opsin expression in the inner retina of a mouse model of retinal degeneration ( rd1 ). Our results reveal that these two strategies (targeting either arrestin binding or Schiff-base hydrolysis) can produce more time-delimited opsin signalling under heterologous expression and establish the potential of this approach to improve optogenetic performance.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Episodic population fragmentation and gene flow reveal a trade‐off between heterozygosity and allelic richness - Peta Hill; Chris R. Dickman; Russell Dinnage; Richard P. Duncan; Scott V. Edwards; Aaron Greenville; Stephen D. Sarre; Emily J. Stringer; Glenda M. Wardle; Bernd Gruber (Molecular Ecology, 2023)
In episodic environments like deserts, populations of some animal species exhibit irregular fluctuations such that populations are alternately large and connected or small and isolated. Such dynamics are typically driven by periodic resource pulses due, for example, to large but infrequent rainfall events. The repeated population bottlenecks resulting from fragmentation should lower genetic diversity over time, yet species undergoing these fluctuations appear to maintain high levels of genetic diversity. To resolve this apparent paradox, we simulated a metapopulation of constant size undergoing repeat episodes of fragmentation and change in gene flow to mimic outcomes experienced by mammals in an Australian desert. We show that episodic fragmentation and gene flow have contrasting effects on two measures of genetic diversity: heterozygosity and allelic richness. Specifically, fragmentation into many, small subpopulations, coupled with periods of infrequent gene flow, preserves allelic richness at the expense of heterozygosity. In contrast, fragmentation into a few, large subpopulations maintains heterozygosity at the expense of allelic richness. The strength of the trade‐off between heterozygosity and allelic richness depends on the amount of gene flow and the frequency of gene flow events. Our results imply that the type of genetic diversity maintained among species living in strongly fluctuating environments will depend on the way populations fragment, with our results highlighting different mechanisms for maintaining allelic richness and heterozygosity in small, fragmented populations.

Light to moderate long-term grazing enhances ecosystem carbon across a broad climatic gradient in northern temperate grasslands - Edward W. Bork; Daniel B. Hewins; Eric G. Lamb; Cameron N. Carlyle; Mark P. Lyseng; Scott X. Chang; Michael J. Alexander; Walter D. Willms; Majid Iravani (Science of The Total Environment, 2023)

LP-25: The curious case of Adverse Outcome Pathways: the stressor agnostic approach bridging disciplines by embracing evidence from diverse initiating factors - J. Filipovska; L.-A. Clerbaux; A. Carusi; M.-J. Amorim; P. Nymark; V. Chauhan; M. Sachana; A. Beronius; S.W. Edwards; C. Wittwehr (Toxicology Letters, 2023)

A review of the nature and source of nutrient impairment in small streams: a desk based characterisation for targeted mitigation measures - Sinéad C. Hogan; John J. O’Sullivan; Michael Bruen; Helen P. Jarvie; Edward J. Cox; Mike J. Bowes; Mary Kelly-Quinn (Hydrobiologia, 2023)

Mechanisms and models for industry engagement in collaborative research in commercial fisheries - Matthew R. Baker; Robert Alverson; Ruth Christiansen; Keith Criddle; Danny Eilertsen; Robert J. Foy; John Gauvin; Scott E. Goodman; Leigh Habegger; Bradley P. Harris; Nicole Kimball; Anna Malek Mercer; et al. (Frontiers in Marine Science, 2023)
Data and insights from fishers are essential sources of information to advance understanding of fishery and ecosystem dynamics. Incorporating fisher and industry knowledge holds prospects for improving marine science and fisheries management. We address cooperative research in the context of collaboration between fishers, scientists, industries, universities, and agencies to develop applied research to understand marine ecosystems, inform fishery management, enhance sustainability, govern resource use, and investigate social-economic dynamics. We leverage the insights of more than 100 research scientists, fisheries managers, industry representatives, and fishers to outline actionable recommendations for effective approaches and mechanisms to integrate industry data, perspectives, and insights in fisheries science. We also highlight opportunities and address challenges and limitations to such collaboration.

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Sequence Divergence in Venom Genes Within and Between Montane Pitviper (Viperidae: Crotalinae: Cerrophidion) Species is Driven by Mutation–Drift Equilibrium - Ramses Alejandro Rosales-García; Rhett M. Rautsaw; Erich P. Hofmann; Christoph I. Grünwald; Hector Franz-Chavez; Ivan T. Ahumada-Carrillo; Ricardo Ramirez-Chaparro; Miguel Angel de la Torre-Loranca; Jason L. Strickland; Andrew J. Mason; Matthew L. Holding; Miguel Borja; et al. (Journal of Molecular Evolution, 2023)

Adaptive, multi-paddock, rotational grazing management alters foraging behavior and spatial grazing distribution of free-ranging cattle - David J. Augustine; Sean P. Kearney; Edward J. Raynor; Lauren M. Porensky; Justin D. Derner (Agriculture, Ecosystems & Environment, 2023)

Marine nutrient subsidies promote biogeochemical hotspots in undisturbed, highly humic estuaries - Chris D. Evans; Stacey L. Felgate; Steffi Carter; Mark Stinchcombe; Edward Mawji; Andrew P. Rees; Inma Lebron; Richard Sanders; Paul Brickle; Daniel J. Mayor (Limnology and Oceanography, 2023)
The land‐ocean dissolved organic carbon (DOC) flux represents a significant term within the global carbon budget, with peatland‐dominated regions representing the most intense sources of terrestrial DOC export. As the interface between freshwater and marine systems, estuaries have the potential to act as a filter of the land‐ocean carbon flux, removing terrestrially derived DOC, which is present at low concentrations in the oceans, via a combination of physicochemical and biological processes. However, the fate of peat‐derived DOC within estuaries remains poorly quantified, partly due to the complicating influences of heterogeneous soils, land‐use, point sources, and upstream modification of organic matter. To minimize these modifying factors, we studied DOC and inorganic nutrients in four small, peat‐dominated, minimally disturbed, and oligotrophic Falkland Island estuaries. Contrary to expectations, we found limited evidence of physicochemical estuarine DOC removal, and instead observed apparent “hot zones” of biogeochemical activity, where terrestrially‐derived silicate mixed with inorganic nitrogen and phosphorus entering the estuaries from the nutrient‐rich marine ecosystem. In two estuaries, this coincided with apparent in situ DOC production. We suggest that the observed phenomena of marine nutrient subsidy of estuarine productivity, and flexible utilization of multiple nutrients within the oligotrophic system, may once have been widespread in temperate estuaries. However, this function has been lost in many ecosystems due to catchment eutrophication by agricultural and urban development. We conclude that the estuaries of the Falkland Islands provide a valuable pre‐disturbance analogue for natural biogeochemical functioning in temperate estuaries receiving high organic matter inputs.

Phylogeography of the Asian green mussel, Perna viridis: pronounced regional genetic differentiation is explained by major freshwater input into the Bay of Bengal - Jonathan P. A. Gardner; Jamila Patterson; Edward J. K. Patterson (Frontiers in Marine Science, 2023)
The Asian green mussel (AGM), Perna viridis , is a mussel of ecological and economic importance throughout much of the tropical and subtropical regions of Asia, from China and Korea in the east to Oman on the Arabian Peninsula in the west. We collated published DNA sequence data and then analysed 467 bp of cytochrome c oxidase I gene (COI) sequence variation from 649 mussels (576 from SE Asia and 73 from India) to test for regional differentiation. Analysis of molecular variation, a haplotype network and a neighbour-joining tree all revealed significant differentiation between mussels from India and those from SE Asia. We observed a greater number of segregating sites (haplotypes) and private haplotypes than expected for Indian mussels compared to SE Asian mussels, based on the respective sample sizes. Tests of neutrality revealed population expansion or a recent selective sweep for only the mussels from India. We suggest that the differentiation of the Indian from the SE Asian mussels is explained by the pronounced seasonal input of freshwater into the northern Bay of Bengal area, which acts as a (semi-permeable) barrier to gene flow between the two regions (i.e., east versus west of the Bay). This suggestion is based on the oceanography of the region and is consistent with the biogeography and reports of genetic breaks in a range of taxa in this region. Further targetted sampling of AGMs from the east coast of India, Bangladesh and Myanmar is required to test this hypothesis, and additional sampling of AGMs from west of India (e.g., Pakistan, Iran, the Arabian Peninsula) will also be informative. Finally, this study is based on the analysis of a single marker (COI) because this is all that is presently available from published sources but we note that the application of new molecular markers such as single nucleotide polymorphisms to newly collected mussel samples will greatly advance our understanding of the AGM genetic discontinuity and its age, and help test its geographical location and its nature (e.g., a steep/shallow cline or a stepped cline).

Greener residential environment is associated with increased bacterial diversity in outdoor ambient air - Jennifer N. Styles; Andrey I. Egorov; Shannon M. Griffin; Jo Klein; J.W. Scott; Elizabeth A. Sams; Edward Hudgens; Chris Mugford; Jill R. Stewart; Kun Lu; Ilona Jaspers; Scott P. Keely; et al. (Science of The Total Environment, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Fine particulate matter and incident coronary heart disease events up to 10 years of follow-up among Deepwater Horizon oil spill workers - Dazhe Chen; Dale P. Sandler; Alexander P. Keil; Gerardo Heiss; Eric A. Whitsel; Gregory C. Pratt; Patricia A. Stewart; Mark R. Stenzel; Caroline P. Groth; Sudipto Banerjee; Tran B. Huynh; Jessie K. Edwards; et al. (Environmental Research, 2023)

Ground-motion prediction models for induced earthquakes in the Groningen gas field, the Netherlands - Julian J. Bommer; Peter J. Stafford; Elmer Ruigrok; Adrian Rodriguez-Marek; Michail Ntinalexis; Pauline P. Kruiver; Benjamin Edwards; Bernard Dost; Jan van Elk (Journal of Seismology, 2022)
Small-magnitude earthquakes induced by gas production in the Groningen field in the Netherlands have prompted the development of seismic risk models that serve both to estimate the impact of these events and to explore the efficacy of different risk mitigation strategies. A core element of the risk modelling is ground-motion prediction models (GMPM) derived from an extensive database of recordings obtained from a dense network of accelerographs installed in the field. For the verification of damage claims, an empirical GMPM for peak ground velocity (PGV) has been developed, which predicts horizontal PGV as a function of local magnitude, M L ; hypocentral distance, R hyp ; and the time-averaged shear-wave velocity over the upper 30 m, V S30 . For modelling the risk due to potential induced and triggered earthquakes of larger magnitude, a GMPM for response spectral accelerations has been developed from regressions on the outputs from finite-rupture simulations of motions at a deeply buried rock horizon. The GMPM for rock motions is coupled with a zonation map defining frequency-dependent non-linear amplification factors to obtain estimates of surface motions in the region of thick deposits of soft soils. The GMPM for spectral accelerations is formulated within a logic-tree framework to capture the epistemic uncertainty associated with extrapolation from recordings of events of M L ≤ 3.6 to much larger magnitudes.

Uterine fibroid polygenic risk score (PRS) associates and predicts risk for uterine fibroid - Jacqueline A. Piekos; Jacklyn N. Hellwege; Yanfei Zhang; Eric S. Torstenson; Gail P. Jarvik; Ozan Dikilitas; Iftikhar J. Kullo; Daniel J. Schaid; David R. Crosslin; Sarah A. Pendergrass; Ming Ta Michael Lee; Dan Roden; et al. (Human Genetics, 2022)

Stress induces major depressive disorder by a neutral sphingomyelinase 2-mediated accumulation of ceramide-enriched exosomes in the blood plasma - Fabian Schumacher; Alexander Carpinteiro; Michael J. Edwards; Gregory C. Wilson; Simone Keitsch; Matthias Soddemann; Barbara Wilker; Burkhard Kleuser; Katrin Anne Becker; Christian P. Müller; Johannes Kornhuber; Erich Gulbins (Journal of Molecular Medicine, 2022)
Major depressive disorder (MDD) is a very common, severe disease with a lifetime prevalence of ~ 10%. The pathogenesis of MDD is unknown and, unfortunately, therapy is often insufficient. We have previously reported that ceramide levels are increased in the blood plasma of patients with MDD and in mice with experimental MDD. Here, we demonstrate that ceramide-enriched exosomes in the blood plasma are increased in mice with stress-induced MDD. Genetic studies reveal that neutral sphingomyelinase 2 is required for the formation of ceramide-enriched exosomes in the blood plasma. Accordingly, induced deficiency of neutral sphingomyelinase 2 prevented mice from the development of stress-induced MDD. Intravenous injection of microparticles from mice with MDD or injection of ceramide-loaded exosomes induced MDD-like behavior in untreated mice, which was abrogated by ex vivo pre-incubation of purified exosomes with anti-ceramide antibodies or ceramidase. Mechanistically, injection of exosomes from mice with MDD or injection of ex vivo ceramide-loaded microparticles inhibited phospholipase D (PLD) in endothelial cells in vitro and in the hippocampus in vivo and thereby decreased phosphatidic acid in the hippocampus, which has been previously shown to mediate MDD by plasma ceramide. In summary, our data indicate that ceramide-enriched exosomes are released by neutral sphingomyelinase 2 into the blood plasma upon stress and mediate stress-induced MDD. Key messages Stress induces ceramide-enriched exosomes in the blood plasma. Ceramide-enriched exosomes mediate major depressive disorder (MDD). Deficiency of neutral sphingomyelinase 2 protects from stress-induced MDD. Neutralization or digestion of ceramide in exosomes prevents stress-induced MDD. Ceramide-enriched exosomes inhibit endothelial phospholipase D in the hippocampus.

Cancer clinical trials in the Philippines - Michelle Ann B. Eala; Patricia Anne S. Basilio; Edward Christopher Dee; Reno Eufemon P. Cereno; Christian Daniel Ang; Nikko J. Magsanoc; Frederic Ivan L. Ting; Dennis L. Sacdalan (Cancer Causes & Control, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The impacts of climate change and post bleaching effects on the octocoral communities of Gulf of Mannar, India - Mahalakshmi Boopathi; P Dinesh Kumar; J K Patterson Edward (Journal of Earth System Science, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Healthy Aging Requires a Healthy Home Care Workforce: the Occupational Safety and Health of Home Care Aides - M. M. Quinn; P. K. Markkanen; C. J. Galligan; S. R. Sama; J. E. Lindberg; M. F. Edwards (Current Environmental Health Reports, 2021)
Purpose of Review To identify important home care (HC) aide occupational safety and health (OSH) hazards and examine how addressing these can improve aide health and the delivery of HC services overall. Specifically, this review seeks to answer: Why is HC aide OSH important? What are the most significant OSH challenges? How can improving HC aide OSH also improve the safety and health of their clients? What implications do the findings have for future research? Recent Findings HC is one of the fastest growing US industries. Aides comprise its largest workforce and are increasingly needed to care for the rapidly aging population. There is an aide shortage due in part to instabilities in HC work organization and to serious job-specific hazards, resulting in aides losing work time. Recent social, economic, and technological factors are rapidly changing the nature of HC work, creating OSH hazards similar to those found in nursing homes. At the same time, aides are experiencing social and economic inequities that increase their vulnerability to OSH hazards. These hazards are also a burden on employers who are challenged to recruit, retain, and train aides. OSH injuries and illness interrupt the continuity of care delivery to clients. Many OSH hazards also put HC clients and families at risk. Summary A new framework and methodologies are needed to assess aide and client safety together in order to guide future HC research, policies, and practices. Government, industry, and labor commitment is needed to fund and coordinate a comprehensive, multidisciplinary research program.

RAD‐sequencing reveals patterns of diversification and hybridization, and the accumulation of reproductive isolation in a clade of partially sympatric, tropical island trees - Alexander G. Linan; Porter P. Lowry; Allison J. Miller; George E. Schatz; Jean‐Claude Sevathian; Christine E. Edwards (Molecular Ecology, 2021)
A common pattern observed in temperate tree clades is that species are often morphologically distinct and partially interfertile but maintain species cohesion despite ongoing hybridization where ranges overlap. Although closely related species commonly occur in sympatry in tropical ecosystems, little is known about patterns of hybridization within a clade over time, and the implications of this hybridization for the maintenance of species boundaries. In this study, we focused on a clade of sympatric trees in the genus Diospyros in the Mascarene islands and investigated whether species are genetically distinct, whether they hybridize, and how patterns of hybridization are related to the time since divergence among species. We sampled multiple populations from each of 12 Mascarene Diospyros species, generated genome‐wide single nucleotide polymorphism data using 2bRADseq, and conducted population genomic and phylogenomic analyses. We found that Mascarene Diospyros species diverged millions of years ago and are today largely genetically distinct from one another. Although hybridization was observed between closely related species belonging to the same subclade, more distantly related species showed little evidence of interspecific hybridization. Phylogenomic analyses also suggested that introgression has occurred during the evolutionary history of the clade. This suggests that, as diversification progressed, interspecific hybridization occurred among species, but became infrequent as lineages diverged from one another and evolved reproductive barriers. Species now coexist in partial sympatry, and experience limited hybridization between close relatives. Additional research is needed to better understand the role that introgression may have played in adaptation and diversification of Mascarene Diospyros , and its relevance for conservation.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Revisiting the Colletotrichum species causing anthracnose of almond in Australia - D. D. de Silva; R. C. Mann; J. Kaur; P. N Ekanayake; T. I Sawbridge; S. McKay; P. W. J. Taylor; J. Edwards (Australasian Plant Pathology, 2021)

The Essentials of Marine Biotechnology - Ana Rotter; Michéle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Jerónimo Chirivella-Martorell; Meltem Conk Dalay; Mercedes Cueto; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Coastal countries have traditionally relied on the existing marine resources (e.g., fishing, food, transport, recreation, and tourism) as well as tried to support new economic endeavors (ocean energy, desalination for water supply, and seabed mining). Modern societies and lifestyle resulted in an increased demand for dietary diversity, better health and well-being, new biomedicines, natural cosmeceuticals, environmental conservation, and sustainable energy sources. These societal needs stimulated the interest of researchers on the diverse and underexplored marine environments as promising and sustainable sources of biomolecules and biomass, and they are addressed by the emerging field of marine (blue) biotechnology. Blue biotechnology provides opportunities for a wide range of initiatives of commercial interest for the pharmaceutical, biomedical, cosmetic, nutraceutical, food, feed, agricultural, and related industries. This article synthesizes the essence, opportunities, responsibilities, and challenges encountered in marine biotechnology and outlines the attainment and valorization of directly derived or bio-inspired products from marine organisms. First, the concept of bioeconomy is introduced. Then, the diversity of marine bioresources including an overview of the most prominent marine organisms and their potential for biotechnological uses are described. This is followed by introducing methodologies for exploration of these resources and the main use case scenarios in energy, food and feed, agronomy, bioremediation and climate change, cosmeceuticals, bio-inspired materials, healthcare, and well-being sectors. The key aspects in the fields of legislation and funding are provided, with the emphasis on the importance of communication and stakeholder engagement at all levels of biotechnology development. Finally, vital overarching concepts, such as the quadruple helix and Responsible Research and Innovation principle are highlighted as important to follow within the marine biotechnology field. The authors of this review are collaborating under the European Commission-funded Cooperation in Science and Technology (COST) Action Ocean4Biotech – European transdisciplinary networking platform for marine biotechnology and focus the study on the European state of affairs.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Ontogenetic scaling of the gastrointestinal tract of a marsupial foregut fermenter, the western grey kangaroo Macropus fuliginosus melanops - Adam J. Munn; Edward P. Snelling; David A. Taggart; Roger S. Seymour (Journal of Comparative Physiology B, 2021)

Perlecan Domain-V Enhances Neurogenic Brain Repair After Stroke in Mice - Amanda L. Trout; Michael P. Kahle; Jill M. Roberts; Aileen Marcelo; Leon de Hoog; Jeffery A. Boychuk; Stephen L. Grupke; Antonio Berretta; Emma K. Gowing; Carie R. Boychuk; Amanda A. Gorman; Danielle N. Edwards; et al. (Translational Stroke Research, 2021)
The extracellular matrix fragment perlecan domain V is neuroprotective and functionally restorative following experimental stroke. As neurogenesis is an important component of chronic post-stroke repair, and previous studies have implicated perlecan in developmental neurogenesis, we hypothesized that domain V could have a broad therapeutic window by enhancing neurogenesis after stroke. We demonstrated that domain V is chronically increased in the brains of human stroke patients, suggesting that it is present during post-stroke neurogenic periods. Furthermore, perlecan deficient mice had significantly less neuroblast precursor cells after experimental stroke. Seven-day delayed domain V administration enhanced neurogenesis and restored peri-infarct excitatory synaptic drive to neocortical layer 2/3 pyramidal neurons after experimental stroke. Domain V’s effects were inhibited by blockade of α2β1 integrin, suggesting the importance of α2β1 integrin to neurogenesis and domain V neurogenic effects. Our results demonstrate that perlecan plays a previously unrecognized role in post-stroke neurogenesis and that delayed DV administration after experimental stroke enhances neurogenesis and improves recovery in an α2β1 integrin-mediated fashion. We conclude that domain V is a clinically relevant neuroprotective and neuroreparative novel stroke therapy with a broad therapeutic window.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Spatial analysis of urine zinc (Zn) concentration for women of reproductive age and school age children in Malawi - Felix P. Phiri; E. Louise Ander; R. Murray Lark; Edward J. M. Joy; Alexander A. Kalimbira; Parminder S. Suchdev; Jellita Gondwe; Elliott M. Hamilton; Michael J. Watts; Martin R. Broadley (Environmental Geochemistry and Health, 2021)
Zinc (Zn) is an essential micronutrient, and Zn deficiency remains a major global public health challenge. Recognised biomarkers of population Zn status include blood plasma or serum Zn concentration and proxy data such as dietary Zn intake and prevalence of stunting. Urine Zn concentration is rarely used to assess population Zn status. This study assessed the value of urine Zn concentration as a biomarker of population Zn status using a nationally representative sample of non-pregnant women of reproductive age (WRA) and school-aged children (SAC) in Malawi. Spot (casual) urine samples were collected from 741 WRA and 665 SAC. Urine Zn concentration was measured by inductively coupled plasma mass spectrometry with specific gravity adjustment for hydration status. Data were analysed using a linear mixed model with a spatially correlated random effect for between-cluster variation. The effect of time of sample collection (morning or afternoon), and gender (for SAC), on urine Zn concentration were examined. There was spatial dependence in urine Zn concentration between clusters among SAC but not WRA, which indicates that food system or environmental factors can influence urine Zn concentration. Mapping urine Zn concentration could potentially identify areas where the prevalence of Zn deficiency is greater and thus where further sampling or interventions might be targeted. There was no evidence for differences in urine Zn concentration between gender ( P = 0.69) or time of sample collection ( P = 0.85) in SAC. Urine Zn concentration was greater in afternoon samples for WRA ( P = 0.003). Relationships between urine Zn concentration, serum Zn concentration, dietary Zn intake, and potential food systems covariates warrant further study.

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

High Energy Side and Rear American Football Head Impacts Cause Obvious Performance Decrement on Video - Adam J. Bartsch; Daniel Hedin; Jay Alberts; Edward C. Benzel; Jason Cruickshank; Robert S. Gray; Kenneth Cameron; Megan N. Houston; Tyler Rooks; Gerald McGinty; Erick Kozlowski; Steven Rowson; et al. (Annals of Biomedical Engineering, 2020)

Historical biogeography of smoothhound sharks (genus Mustelus ) of Southern Africa reveals multiple dispersal events from the Northern Hemisphere - Simo N. Maduna; Kelvin L. Hull; Edward D. Farrell; Jessica J. Boomer; Ana Veríssimo; Ilaria A. M. Marino; Carlotta Mazzoldi; Lorenzo Zane; Sabine P. Wintner; Mikhail V. Chesalin; Charlene da Silva; Chrysoula Gubili; et al. (Systematics and Biodiversity, 2020)

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

Transient protein expression in tobacco BY-2 plant cell packs using single and multi-cassette replicating vectors - Zuzana Poborilova; Helena Plchova; Noemi Cerovska; Cornelius J. Gunter; Inga I. Hitzeroth; Edward P. Rybicki; Tomas Moravec (Plant Cell Reports, 2020)
Key message This is the first evidence that replicating vectors can be successfully used for transient protein expression in BY-2 plant cell packs. Abstract Transient recombinant protein expression in plants and recently also plant cell cultures are of increasing interest due to the speed, safety and scalability of the process. Currently, studies are focussing on the design of plant virus-derived vectors to achieve higher amounts of transiently expressed proteins in these systems. Here we designed and tested replicating single and multi-cassette vectors that combine elements for enhanced replication and hypertranslation, and assessed their ability to express and particularly co-express proteins by Agrobacterium -mediated transient expression in tobacco BY-2 plant cell packs. Substantial yields of green and red fluorescent proteins of up to ~ 700 ng/g fresh mass were detected in the plant cells along with position-dependent expression. This is the first evidence of the ability of replicating vectors to transiently express proteins in BY-2 plant cell packs.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Eroding islands of Gulf of Mannar, Southeast India: a consequence of long-term impact of coral mining and climate change - N. Gladwin Gnana Asir; P. Dinesh Kumar; A. Arasamuthu; G. Mathews; K. Diraviya Raj; T. K. Ashok Kumar; Deepak S. Bilgi; J. K. Patterson Edward (Natural Hazards, 2020)

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Exploiting the genome of Thinopyrum elongatum to expand the gene pool of hexaploid wheat - Lauren Baker; Surbhi Grewal; Cai-yun Yang; Stella Hubbart-Edwards; Duncan Scholefield; Stephen Ashling; Amanda J. Burridge; Alexandra M. Przewieslik-Allen; Paul A. Wilkinson; Ian P. King; Julie King (Theoretical and Applied Genetics, 2020)
Key message One hundred and thirty four introgressions from Thinopyrum elongatum have been transferred into a wheat background and were characterised using 263 SNP markers. Abstract Species within the genus Thinopyrum have been shown to carry genetic variation for a very wide range of traits including biotic and abiotic stresses and quality. Research has shown that one of the species within this genus, Th. elongatum , has a close relationship with the genomes of wheat making it a highly suitable candidate to expand the gene pool of wheat. Homoeologous recombination, in the absence of the Ph1 gene, has been exploited to transfer an estimated 134 introgressions from Th. elongatum into a hexaploid wheat background. The introgressions were detected and characterised using 263 single nucleotide polymorphism markers from a 35 K Axiom ® Wheat-Relative Genotyping Array, spread across seven linkage groups and validated using genomic in situ hybridisation. The genetic map had a total length of 187.8 cM and the average chromosome length was 26.8 cM. Comparative analyses of the genetic map of Th. elongatum and the physical map of hexaploid wheat confirmed previous work that indicated good synteny at the macro-level, although Th. elongatum does not contain the 4A/5A/7B translocation found in wheat.

The Rapid Regenerative Response of a Model Sea Anemone Species Exaiptasia pallida Is Characterised by Tissue Plasticity and Highly Coordinated Cell Communication - Chloé A. van der Burg; Ana Pavasovic; Edward K. Gilding; Elise S. Pelzer; Joachim M. Surm; Hayden L. Smith; Terence P. Walsh; Peter J. Prentis (Marine Biotechnology, 2020)

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The impact of secondary forest regeneration on ground-dwelling ant communities in the Tropical Andes - Matthew G. Hethcoat; Bethany J. King; Fernando Fernandez Castiblanco; Claudia M. Ortiz-Sepúlveda; Fabian Camilo Prada Achiardi; Felicity A. Edwards; Claudia Medina; James J. Gilroy; Torbjørn Haugaasen; David P. Edwards (Oecologia, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Sphingosine-coating of plastic surfaces prevents ventilator-associated pneumonia - Aaron P. Seitz; Fabian Schumacher; Jennifer Baker; Matthias Soddemann; Barbara Wilker; Charles C. Caldwell; Ryan M. Gobble; Markus Kamler; Katrin Anne Becker; Sascha Beck; Burkhard Kleuser; Michael J. Edwards; et al. (Journal of Molecular Medicine, 2019)

Addressing limitations in existing ‘simplified’ liquefaction triggering evaluation procedures: application to induced seismicity in the Groningen gas field - R. A. Green; J. J. Bommer; A. Rodriguez-Marek; B. W. Maurer; P. J. Stafford; B. Edwards; P. P. Kruiver; G. de Lange; J. van Elk (Bulletin of Earthquake Engineering, 2019)

Simulations for the development of a ground motion model for induced seismicity in the Groningen gas field, The Netherlands - B. Edwards; B. Zurek; E. van Dedem; P. J. Stafford; S. Oates; J. van Elk; B. deMartin; J. J. Bommer (Bulletin of Earthquake Engineering, 2019)

Late Holocene environmental changes and anthropogenic impact in Dee Why Lagoon, New South Wales - C. Chagué; D. Edwards; J. Ruszczyk; P. Gadd; A. Zawadzki; G. Jacobsen; D. Fierro; J. Goralewski; L. Clement; A. Albani (Australian Journal of Earth Sciences, 2019)

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Comparison of metabolomic responses of earthworms to sub-lethal imidacloprid exposure in contact and soil tests - Vivek D. Dani; Brian P. Lankadurai; Edward G. Nagato; André J. Simpson; Myrna J. Simpson (Environmental Science and Pollution Research, 2019)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Development and validation of an exome-based SNP marker set for identification of the St, Jr and Jvs genomes of Thinopyrym intermedium in a wheat background - Andras Cseh; Caiyun Yang; Stella Hubbart-Edwards; Duncan Scholefield; Stephen S. Ashling; Amanda J. Burridge; Paul A. Wilkinson; Ian P. King; Julie King; Surbhi Grewal (Theoretical and Applied Genetics, 2019)

Land‐sparing agriculture sustains higher levels of avian functional diversity than land sharing - Patrick G. Cannon; James J. Gilroy; Joseph A. Tobias; Alex Anderson; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2019)
The ecological impacts of meeting rising demands for food production can potentially be mitigated by two competing land‐use strategies: off‐setting natural habitats through intensification of existing farmland (land sparing), or elevating biodiversity within the agricultural matrix via the integration of “wildlife‐friendly” habitat features (land sharing). However, a key unanswered question is whether sparing or sharing farming would best conserve functional diversity, which can promote ecosystem stability and resilience to future land‐use change. Focusing on bird communities in tropical cloud forests of the Colombian Andes, we test the performance of each strategy in conserving functional diversity. We show that multiple components of avian functional diversity in farmland are positively related to the proximity and extent of natural forest. Using landscape and community simulations, we also show that land‐sparing agriculture conserves greater functional diversity and predicts higher abundance of species supplying key ecological functions than land sharing, with sharing becoming progressively inferior with increasing isolation from remnant forest. These results suggest low‐intensity agriculture is likely to conserve little functional diversity unless large blocks of adjacent natural habitat are protected, consistent with land sparing. To ensure the retention of functionally diverse ecosystems, we urgently need to implement mechanisms for increasing farmland productivity whilst protecting spared land.

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Pharmacokinetics and safety of glecaprevir and pibrentasvir in HCV-negative subjects with hepatic impairment - Matthew P. Kosloski; Haoyu Wang; David Pugatch; Federico J. Mensa; Edward Gane; Eric Lawitz; Thomas C. Marbury; Richard A. Preston; Jens Kort; Wei Liu (European Journal of Clinical Pharmacology, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

Identification of a metallothionein gene in honey bee Apis mellifera and its expression profile in response to Cd, Cu and Pb exposure - Jelena Purać; Tatjana V. Nikolić; Danijela Kojić; Anđelka S. Ćelić; Jovana J. Plavša; Duško P. Blagojević; Edward T. Petri (Molecular Ecology, 2019)
Metallothioneins are ubiquitous proteins important in metal homeostasis and detoxification. However, they have not previously been identified in honey bees or other Hymenoptera, where metallothioneins could be of ecophysiological and ecotoxicological significance. Better understanding of the molecular responses to stress induced by toxic metals could contribute to honey bee conservation. In addition, honey bee metallothionein could represent a biomarker for monitoring environmental quality. Here we identify and characterize a metallothionein gene in Apis mellifera ( AmMT ). AmMT is 1,680 bp long and encodes a 48 amino acids protein with 15 cysteines and no aromatic residues. A metal response element upstream of the start codon, coupled with numerous cis ‐regulatory elements indicate the functional context of AmMT. Molecular modelling predicts several transition metal binding sites, and comparative phylogenetic analysis revealed five putative metallothionein proteins in three other hymenoptera species. AmMT was characterized by cloning the full‐length coding sequence of the putative metallothionein. Recombinant AmMT was found to increase metal tolerance upon overexpression in Escherichia coli supplemented with Cd, Cu or Pb. Finally, in laboratory tests on honey bees, gene expression profiles showed a dose‐dependant relationship between Cd, Cu and Pb concentrations present in food and AmMT expression, while field experiments showed induction of AmMT in bees from an industrial site compared to those from an urban area. These studies suggest that AmMT has metal binding properties in agreement with a possible role in metal homeostasis. Further functional and structural characterization of metallothionein in honey bees and other Hymenoptera are necessary.

Impacts of tropical forest disturbance on species vital rates - Cindy C.P. Cosset; James J. Gilroy; David P. Edwards (Conservation Biology, 2019)
Tropical forests are experiencing enormous threats from deforestation and habitat degradation. Much knowledge of the impacts of these land‐use changes on tropical species comes from studies examining patterns of richness and abundance. Demographic vital rates (survival, reproduction, and movement) can also be affected by land‐use change in a way that increases species vulnerability to extirpation, but in many cases these impacts may not be manifested in short‐term changes in abundance or species richness. We conducted a literature review to assess current knowledge and research effort concerning how land‐use change affects species vital rates in tropical forest vertebrates. We found a general paucity of empirical research on demography across taxa and regions, with some biases toward mammals and birds and land‐use transitions, including fragmentation and agriculture. There is also considerable between‐species variation in demographic responses to land‐use change, which could reflect trait‐based differences in species sensitivity, complex context dependencies (e.g., between‐region variation), or inconsistency in methods used in studies. Efforts to improve understanding of anthropogenic impacts on species demography are underway, but there is a need for increased research effort to fill knowledge gaps in understudied tropical regions and taxa. The lack of information on demographic impacts of anthropogenic disturbance makes it difficult to draw definite conclusions about the magnitude of threats to tropical ecosystems under anthropogenic pressures. Thus, determining conservation priorities and improving conservation effectiveness remains a challenge.

Bioassays on the role of tomato, potato and sweet pepper as sources of Tomato chlorosis virus transmitted by Bemisia tabaci MEAM1 - T. Mituti; J. P. Edwards Molina; J. A. M. Rezende (European Journal of Plant Pathology, 2018)

Does sowing an oats catch crop reduce nitrate leaching from urine deposition following simulated winter forage grazing? - a growth chamber experiment - P. L. Carey; K. C. Cameron; H. J. Di; G. R. Edwards (Plant and Soil, 2018)

Contemporary and emerging fisheries in The Bahamas—Conservation and management challenges, achievements and future directions - Krista D. Sherman; Aaron D. Shultz; Craig P. Dahlgren; Claire Thomas; Edward Brooks; Annabelle Brooks; Daniel R. Brumbaugh; Lester Gittens; Karen J. Murchie (Fisheries Management and Ecology, 2018)
The harvest of marine resources has long‐standing cultural and economic importance to The Bahamas and other small island developing states. Tourists and residents place a demand on local marine resources, particularly Caribbean spiny lobster , Panulirus argus (Latreille), queen conch, Lobatus gigas (Linnaeus) and Nassau grouper, Epinephelus striatus (Bloch), and many fishery products are also sold on the global market. Illegal, unreported and unregulated fishing coupled with inadequate regulations and enforcement are the main factors contributing to the decline of Bahamian fisheries along with other anthropogenic impacts. This article reviews the status of fisheries management in The Bahamas using economically and ecologically important species as case studies to highlight conservation successes, knowledge gaps and deficiencies in existing management approaches. The review concludes with an examination of how emerging fisheries and improved conservation management strategies have the potential to improve economic and food security throughout the archipelago.

Factors Affecting Disaster Preparedness, Response, and Recovery Using the Community Capitals Framework - Amber Himes-Cornell; Carlos Ormond; Kristin Hoelting; Natalie C. Ban; J. Zachary Koehn; Edward H. Allison; Eric C. Larson; Daniel H. Monson; Henry P. Huntington; Thomas A. Okey (Coastal Management, 2018)

Spatiotemporal heterogeneity and patterning of developing renal blood vessels - Edward Daniel; D. Berfin Azizoglu; Anne R. Ryan; Tezin A. Walji; Christopher P. Chaney; Gabrielle I. Sutton; Thomas J. Carroll; Denise K. Marciano; Ondine Cleaver (Angiogenesis, 2018)

Rapid alterations to marine microbiota communities following an oil spill - Brad J. Gemmell; Hernando P. Bacosa; Ben O. Dickey; Colbi G. Gemmell; Lama R. Alqasemi; Edward J. Buskey (Ecotoxicology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Long-term grazing impacts on vegetation diversity, composition, and exotic species presence across an aridity gradient in northern temperate grasslands - Mark P. Lyseng; Edward W. Bork; Daniel B. Hewins; Mike J. Alexander; Cameron N. Carlyle; Scott X. Chang; Walter D. Willms (Plant Ecology, 2018)

Characterisation of ground motion recording stations in the Groningen gas field - Rik Noorlandt; Pauline P. Kruiver; Marco P. E. de Kleine; Marios Karaoulis; Ger de Lange; Antonio Di Matteo; Julius von Ketelhodt; Elmer Ruigrok; Benjamin Edwards; Adrian Rodriguez-Marek; Julian J. Bommer; Jan van Elk; et al. (Journal of Seismology, 2018)

Characteristics and consequences of lava dome collapse at Ruawahia, Taupo Volcanic Zone, New Zealand - P. A. Ashwell; B. M. Kennedy; M. Edwards; J. W. Cole (Bulletin of Volcanology, 2018)

First evidence for crossbreeding between invasive Iguana iguana and the native rock iguana (Genus Cyclura) on Little Cayman Island - Jeanette B. Moss; Mark E. Welch; Frederic J. Burton; Michael V. Vallee; Edward W. Houlcroft; Tanja Laaser; Glenn P. Gerber (Biological Invasions, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

TOX3 Variants Are Involved in Restless Legs Syndrome and Parkinson’s Disease with Opposite Effects - Sadaf Mohtashami; Qin He; Jennifer A. Ruskey; Sirui Zhou; Patrick A. Dion; Richard P. Allen; Christopher J. Earley; Edward A. Fon; Lan Xiong; Nicolas Dupre; Yves Dauvilliers; Guy A. Rouleau; et al. (Journal of Molecular Neuroscience, 2018)

Characterisation of Thinopyrum bessarabicum chromosomes through genome-wide introgressions into wheat - Surbhi Grewal; Caiyun Yang; Stella Hubbart Edwards; Duncan Scholefield; Stephen Ashling; Amanda J. Burridge; Ian P. King; Julie King (Theoretical and Applied Genetics, 2018)

Army imposters: diversification of army ant-mimicking beetles with their Eciton hosts - S. Pérez-Espona; W. P. Goodall-Copestake; S. M. Berghoff; K. J. Edwards; N. R. Franks (Insectes Sociaux, 2018)

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

A Novel Oral Fluid Assay (LC-QTOF-MS) for the Detection of Fentanyl and Clandestine Opioids in Oral Fluid After Reported Heroin Overdose - Matthew K. Griswold; Peter R. Chai; Alex J. Krotulski; Melissa Friscia; Brittany P. Chapman; Neha Varma; Edward W. Boyer; Barry K. Logan; Kavita M. Babu (Journal of Medical Toxicology, 2017)

Keeping it in the family: strong fine-scale genetic structure and inbreeding in Lodoicea maldivica, the largest-seeded plant in the world - E. J. Morgan; C. N. Kaiser-Bunbury; P. J. Edwards; F. Fleischer-Dogley; C. J. Kettle (Conservation Genetics, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

Facultative CAM photosynthesis (crassulacean acid metabolism) in four species of Calandrinia, ephemeral succulents of arid Australia - Joseph A. M. Holtum; Lillian P. Hancock; Erika J. Edwards; Klaus Winter (Photosynthesis Research, 2017)

Functional connectivity abnormalities and associated cognitive deficits in fetal alcohol Spectrum disorders (FASD) - Jeffrey R. Wozniak; Bryon A. Mueller; Sarah N. Mattson; Claire D. Coles; Julie A. Kable; Kenneth L. Jones; Christopher J. Boys; Kelvin O. Lim; Edward P. Riley; Elizabeth R. Sowell (Brain Imaging and Behavior, 2017)

The tooth, the whole tooth and nothing but the tooth: tooth shape and ontogenetic shift dynamics in the white shark Carcharodon carcharias - G. C. A. French; M. Stürup; S. Rizzuto; J. H. van Wyk; D. Edwards; R. W. Dolan; S. P. Wintner; A. V. Towner; W. O. H. Hughes (Journal of Fish Biology, 2017)
Results from this study of the white shark Carcharodon carcharias include measurements obtained using a novel photographic method that reveal significant differences between the sexes in the relationship between tooth cuspidity and shark total length, and a novel ontogenetic change in male tooth shape. Males exhibit broader upper first teeth and increased distal inclination of upper third teeth with increasing length, while females do not present a consistent morphological change. Substantial individual variation, with implications for pace of life syndrome, was present in males and tooth polymorphism was suggested in females. Sexual differences and individual variation may play major roles in ontogenetic changes in tooth morphology in C. carcharias , with potential implications for their foraging biology. Such individual and sexual differences should be included in studies of ontogenetic shift dynamics in other species and systems.

Assessment of the Neuroprotective Effects of Arginine-Rich Protamine Peptides, Poly-Arginine Peptides (R12-Cyclic, R22) and Arginine–Tryptophan-Containing Peptides Following In Vitro Excitotoxicity and/or Permanent Middle Cerebral Artery Occlusion in Rats - Bruno P. Meloni; Diego Milani; Jane L. Cross; Vince W. Clark; Adam B. Edwards; Ryan S. Anderton; David J. Blacker; Neville W. Knuckey (NeuroMolecular Medicine, 2017)

Qualitative and quantitative factors affecting the relationship between Canola leaf spot epidemic and stem base canker (Leptosphaeria maculans) in Argentina - J. P. Edwards Molina; A. Escande; G. Cendoya; F. Quiroz (Australasian Plant Pathology, 2017)

Genomic footprints of adaptation in a cooperatively breeding tropical bird across a vegetation gradient - Flavia Termignoni‐García; Juan P. Jaramillo‐Correa; Juan Chablé‐Santos; Mark Liu; Allison J. Shultz; Scott V. Edwards; Patricia Escalante‐Pliego (Molecular Ecology, 2017)
Identifying the genetic basis of phenotypic variation and its relationship with the environment is key to understanding how local adaptations evolve. Such patterns are especially interesting among populations distributed across habitat gradients, where genetic structure can be driven by isolation by distance ( IBD ) and/or isolation by environment ( IBE ). Here, we used variation in ~1,600 high‐quality SNP s derived from paired‐end sequencing of double‐digest restriction site‐associated DNA (dd RAD ‐Seq) to test hypotheses related to IBD and IBE in the Yucatan jay ( Cyanocorax yucatanicus) , a tropical bird endemic to the Yucatán Peninsula. This peninsula is characterized by a precipitation and vegetation gradient—from dry to evergreen tropical forests—that is associated with morphological variation in this species. We found a moderate level of nucleotide diversity (π = .008) and little evidence for genetic differentiation among vegetation types. Analyses of neutral and putatively adaptive SNP s (identified by complementary genome‐scan approaches) indicate that IBD is the most reliable explanation to account for frequency distribution of the former, while IBE has to be invoked to explain those of the later. These results suggest that selective factors acting along a vegetation gradient can promote local adaptation in the presence of gene flow in a vagile, nonmigratory and geographically restricted species. The putative candidate SNP s identified here are located within or linked to a variety of genes that represent ideal targets for future genomic surveys.

Optimisation of kelp (Laminaria digitata) gametophyte growth and gametogenesis: effects of photoperiod and culture media - J. J. Ratcliff; A. Soler-Vila; D. Hanniffy; M. P. Johnson; M. D. Edwards (Journal of Applied Phycology, 2017)

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo - Nicolás M. Suárez; Betty Lau; George M. Kemble; Ronzo Lee; Edward S. Mocarski; Gavin W. G. Wilkinson; Stuart P. Adler; Michael A. McVoy; Andrew J. Davison (Virus Genes, 2017)

Litter decay controlled by temperature, not soil properties, affecting future soil carbon - Edward G. Gregorich; Henry Janzen; Benjamin H. Ellert; Bobbi L. Helgason; Budong Qian; Bernie J. Zebarth; Denis A. Angers; Ronald P. Beyaert; Craig F. Drury; Scott D. Duguid; William E. May; Brian G. McConkey; et al. (Global Change Biology, 2017)
Widespread global changes, including rising atmospheric CO 2 concentrations, climate warming and loss of biodiversity, are predicted for this century; all of these will affect terrestrial ecosystem processes like plant litter decomposition. Conversely, increased plant litter decomposition can have potential carbon‐cycle feedbacks on atmospheric CO 2 levels, climate warming and biodiversity. But predicting litter decomposition is difficult because of many interacting factors related to the chemical, physical and biological properties of soil, as well as to climate and agricultural management practices. We applied 13 C‐labelled plant litter to soil at ten sites spanning a 3500‐km transect across the agricultural regions of Canada and measured its decomposition over five years. Despite large differences in soil type and climatic conditions, we found that the kinetics of litter decomposition were similar once the effect of temperature had been removed, indicating no measurable effect of soil properties. A two‐pool exponential decay model expressing undecomposed carbon simply as a function of thermal time accurately described kinetics of decomposition. ( R 2 = 0.94; RMSE = 0.0508). Soil properties such as texture, cation exchange capacity, pH and moisture, although very different among sites, had minimal discernible influence on decomposition kinetics. Using this kinetic model under different climate change scenarios, we projected that the time required to decompose 50% of the litter (i.e. the labile fractions) would be reduced by 1–4 months, whereas time required to decompose 90% of the litter (including recalcitrant fractions) would be reduced by 1 year in cooler sites to as much as 2 years in warmer sites. These findings confirm quantitatively the sensitivity of litter decomposition to temperature increases and demonstrate how climate change may constrain future soil carbon storage, an effect apparently not influenced by soil properties.

Source-Sink Dynamics: a Neglected Problem for Landscape-Scale Biodiversity Conservation in the Tropics - James J. Gilroy; David P. Edwards (Current Landscape Ecology Reports, 2017)

Amazon River influence on nitrogen fixation and export production in the western tropical North Atlantic - Sarah C. Weber; Edward J. Carpenter; Victoria J. Coles; Patricia L. Yager; Joaquim Goes; Joseph P. Montoya (Limnology and Oceanography, 2017)
As part of the ANACONDAS program, we investigated the role of the Amazon plume in stimulating offshore nitrogen fixation and export production during the river's high‐discharge period (May–June 2010). Using the shipboard underway system, we performed high‐resolution sampling of over 450,000 km 2 of surface waters, characterizing the distribution of nutrients, phytoplankton, particulate organic matter (POM), and stable carbon and nitrogen isotopes of POM in the offshore plume. We found distinct regional variations in diazotroph communities, with the Diatom‐Diazotroph Associations (DDA) Hemiaulus hauckii – Richelia intracellularis dominating the low N : P mesohaline waters to the northwest of the plume axis and Trichodesmium spp. primarily occupying oceanic waters to the east. Nutrient availability broadly shaped diazotroph distributions along the salinity gradient, but habitat longevity may also play a role in the finer‐scale distributions of communities, particularly of DDAs. H. hauckii and Trichodesmium spp. affected the nitrogen and carbon budgets in fundamentally different ways within the plume‐influenced regions, with H. hauckii making much greater contributions to the particulate nitrogen pool and to CO 2 drawdown than Trichodesmium spp., leading to much higher export fluxes. Our findings provide an important constraint on the role of the Amazon plume in creating distinct niches and roles for diazotrophs in the nutrient and carbon budgets of the western tropical North Atlantic.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Evolution of a small hydrothermal eruption episode through a mud pool of varying depth and rheology, White Island, NZ - M. J. Edwards; B. M. Kennedy; A. D. Jolly; B. Scheu; P. Jousset (Bulletin of Volcanology, 2017)

Role of polysaccharides in food, digestion, and health - A. Lovegrove; C. H. Edwards; I. De Noni; H. Patel; S. N. El; T. Grassby; C. Zielke; M. Ulmius; L. Nilsson; P. J. Butterworth; P. R Ellis; P. R. Shewry (Critical Reviews in Food Science and Nutrition, 2017)

A high-density SNP genotyping array for Brassica napus and its ancestral diploid species based on optimised selection of single-locus markers in the allotetraploid genome - Wayne E. Clarke; Erin E. Higgins; Joerg Plieske; Ralf Wieseke; Christine Sidebottom; Yogendra Khedikar; Jacqueline Batley; Dave Edwards; Jinling Meng; Ruiyuan Li; Cynthia Taylor Lawley; Jérôme Pauquet; et al. (Theoretical and Applied Genetics, 2016)

Accuracy of Rapid Tests Used for Analysis of Advanced Onsite Wastewater Treatment System Effluent - Brittany V. Lancellotti; Robert J. Bercaw; George W. Loomis; Kevin P. Hoyt; Edward J. Avizinis; Jose A. Amador (Water, Air, & Soil Pollution, 2016)

Use of a coupled soil-root-leaf model to optimise phosphate fertiliser use efficiency in barley - J. Heppell; S. Payvandi; P. Talboys; K. C. Zygalakis; D. Langton; R. Sylvester-Bradley; A. C. Edwards; R. Walker; P. Withers; D. L. Jones; T. Roose (Plant and Soil, 2016)

Intramuscular MAPK signaling following high volume and high intensity resistance exercise protocols in trained men - Adam M. Gonzalez; Jay R. Hoffman; Jeremy R. Townsend; Adam R. Jajtner; Carleigh H. Boone; Kyle S. Beyer; Kayla M. Baker; Adam J. Wells; Gerald T. Mangine; Edward H. Robinson; David D. Church; Leonardo P. Oliveira; et al. (European Journal of Applied Physiology, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Taxon interactions control the distributions of cryoconite bacteria colonizing a High Arctic ice cap - Jarishma K. Gokul; Andrew J. Hodson; Eli R. Saetnan; Tristram D. L. Irvine‐Fynn; Philippa J. Westall; Andrew P. Detheridge; Nozomu Takeuchi; Jennifer Bussell; Luis A. J. Mur; Arwyn Edwards (Molecular Ecology, 2016)
Microbial colonization of glacial ice surfaces incurs feedbacks which affect the melting rate of the ice surface. Ecosystems formed as microbe–mineral aggregates termed cryoconite locally reduce ice surface albedo and represent foci of biodiversity and biogeochemical cycling. Consequently, greater understanding the ecological processes in the formation of functional cryoconite ecosystems upon glacier surfaces is sought. Here, we present the first bacterial biogeography of an ice cap, evaluating the respective roles of dispersal, environmental and biotic filtration occurring at local scales in the assembly of cryoconite microbiota. 16S rRNA gene amplicon semiconductor sequencing of cryoconite colonizing a Svalbard ice cap coupled with digital elevation modelling of physical parameters reveals the bacterial community is dominated by a ubiquitous core of generalist taxa, with evidence for a moderate pairwise distance–decay relationship. While geographic position and melt season duration are prominent among environmental predictors of community structure, the core population of taxa appears highly influential in structuring the bacterial community. Taxon co‐occurrence network analysis reveals a highly modular community structured by positive interactions with bottleneck taxa, predominantly Actinobacteria affiliated to isolates from soil humus. In contrast, the filamentous cyanobacterial taxon (assigned to Leptolyngbya/Phormidesmis pristleyi ) which dominates the community and binds together granular cryoconite are poorly connected to other taxa. While our study targeted one ice cap, the prominent role of generalist core taxa with close environmental relatives across the global cryosphere indicate discrete roles for cosmopolitan Actinobacteria and Cyanobacteria as respective keystone taxa and ecosystem engineers of cryoconite ecosystems colonizing ice caps.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Tree‐mycorrhizal associations detected remotely from canopy spectral properties - Joshua B. Fisher; Sean Sweeney; Edward R. Brzostek; Tom P. Evans; Daniel J. Johnson; Jonathan A. Myers; Norman A. Bourg; Amy T. Wolf; Robert W. Howe; Richard P. Phillips (Global Change Biology, 2016)
A central challenge in global ecology is the identification of key functional processes in ecosystems that scale, but do not require, data for individual species across landscapes. Given that nearly all tree species form symbiotic relationships with one of two types of mycorrhizal fungi – arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) fungi – and that AM ‐ and ECM ‐dominated forests often have distinct nutrient economies, the detection and mapping of mycorrhizae over large areas could provide valuable insights about fundamental ecosystem processes such as nutrient cycling, species interactions, and overall forest productivity. We explored remotely sensed tree canopy spectral properties to detect underlying mycorrhizal association across a gradient of AM ‐ and ECM ‐dominated forest plots. Statistical mining of reflectance and reflectance derivatives across moderate/high‐resolution Landsat data revealed distinctly unique phenological signals that differentiated AM and ECM associations. This approach was trained and validated against measurements of tree species and mycorrhizal association across ~130 000 trees throughout the temperate United States. We were able to predict 77% of the variation in mycorrhizal association distribution within the forest plots ( P

Genomic insights into the carbohydrate catabolism of Cairneyella variabilis gen. nov. sp. nov., the first reports from a genome of an ericoid mycorrhizal fungus from the southern hemisphere - David J. Midgley; Carly P. Rosewarne; Paul Greenfield; Dongmei Li; Cassandra J. Vockler; Catherine J. Hitchcock; Nicole A. Sawyer; Robyn Brett; Jacqueline Edwards; John I. Pitt; Nai Tran-Dinh (Mycorrhiza, 2016)

Combined evidence indicates that Perna indica Kuriakose and Nair 1976 is Perna perna (Linnaeus, 1758) from the Oman region introduced into southern India more than 100 years ago - Jonathan P. A. Gardner; Jamila Patterson; Sanil George; J. K. Patterson Edward (Biological Invasions, 2016)

An integrated pan‐tropical biomass map using multiple reference datasets - Valerio Avitabile; Martin Herold; Gerard B. M. Heuvelink; Simon L. Lewis; Oliver L. Phillips; Gregory P. Asner; John Armston; Peter S. Ashton; Lindsay Banin; Nicolas Bayol; Nicholas J. Berry; Pascal Boeckx; et al. (Global Change Biology, 2016)
We combined two existing datasets of vegetation aboveground biomass ( AGB ) ( Proceedings of the National Academy of Sciences of the United States of America , 108 , 2011, 9899; Nature Climate Change , 2 , 2012, 182) into a pan‐tropical AGB map at 1‐km resolution using an independent reference dataset of field observations and locally calibrated high‐resolution biomass maps, harmonized and upscaled to 14 477 1‐km AGB estimates. Our data fusion approach uses bias removal and weighted linear averaging that incorporates and spatializes the biomass patterns indicated by the reference data. The method was applied independently in areas (strata) with homogeneous error patterns of the input (Saatchi and Baccini) maps, which were estimated from the reference data and additional covariates. Based on the fused map, we estimated AGB stock for the tropics (23.4 N–23.4 S) of 375 Pg dry mass, 9–18% lower than the Saatchi and Baccini estimates. The fused map also showed differing spatial patterns of AGB over large areas, with higher AGB density in the dense forest areas in the Congo basin, Eastern Amazon and South‐East Asia, and lower values in Central America and in most dry vegetation areas of Africa than either of the input maps. The validation exercise, based on 2118 estimates from the reference dataset not used in the fusion process, showed that the fused map had a RMSE 15–21% lower than that of the input maps and, most importantly, nearly unbiased estimates (mean bias 5 Mg dry mass ha −1 vs. 21 and 28 Mg ha −1 for the input maps). The fusion method can be applied at any scale including the policy‐relevant national level, where it can provide improved biomass estimates by integrating existing regional biomass maps as input maps and additional, country‐specific reference datasets.

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Alcohol exposure in utero is associated with decreased gray matter volume in neonates - Kirsten A. Donald; J. P. Fouche; Annerine Roos; Nastassja Koen; Fleur M. Howells; Edward P. Riley; Roger P. Woods; Heather J. Zar; Katherine L. Narr; Dan J. Stein (Metabolic Brain Disease, 2016)

The impact of the introduction of fidaxomicin on the management of Clostridium difficile infection in seven NHS secondary care hospitals in England: a series of local service evaluations - S. D. Goldenberg; S. Brown; L. Edwards; D. Gnanarajah; P. Howard; D. Jenkins; D. Nayar; M. Pasztor; S. Oliver; T. Planche; J. A. T. Sandoe; P. Wade; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Lignin‐modifying processes in the rhizosphere of arid land grasses - Corey M. Hudson; Edward Kirton; Miriam I. Hutchinson; Joanna L. Redfern; Blake Simmons; Eric Ackerman; Seema Singh; Kelly P. Williams; Donald O. Natvig; Amy J. Powell (Environmental Microbiology, 2015)
Summary Genes associated with elevated oxidative enzyme activities in arid systems have not been well characterized. To link measured oxidative activities with specific enzymes, we assembled protein‐coding reads from the rhizospheres ( RHZ ) of two arid land grasses. Targeted gene scans for open reading frames, encoding genes potentially involved in lignin modification, resulted in 127 distinct assembly products. The putative genes included those significantly similar to C lass II secretory fungal peroxidases. These genes are expressed at sufficiently high levels for assembly, annotation and differentiation across experimental conditions, and they demonstrate the interplay of root systems, environment and plant microbiomes. The genes assembled also included copper‐dependent lytic polysaccharide monooxygenases. We detail the enzymes in the host grass RHZs and present a preliminary taxonomic microhabitat characterization. Our findings provide support for biologically mediated Fenton chemistry in the root zones of desert grasses, and provide insight into arid land carbon flow. These results also demonstrate a hyperdiverse microbial community. Both ribosomal RNA and messenger RNA sequences were dominated by bacteria, followed by fungal sequence abundance. Among the notable fungal sequences were those from the members of the arbuscular mycorrhizal fungi ( G lomeromycota), which though abundant in this study, we rarely observed in previous PCR ‐based surveys.

Defining adult bonefish (Albula vulpes) movement corridors around Grand Bahama in the Bahamian Archipelago - Karen J. Murchie; Aaron D. Shultz; Jeffrey A. Stein; Steven J. Cooke; Justin Lewis; Jason Franklin; Greg Vincent; Edward J. Brooks; Julie E. Claussen; David P. Philipp (Environmental Biology of Fishes, 2015)

Fostering effective international collaboration for marine science in small island states - Edward J. Hind; Steven M. Alexander; Stephanie J. Green; Jacob P. Kritzer; Michael J. Sweet; Ayana Elizabeth Johnson; Fabian P. Amargós; Nicola S. Smith; Angelie M. Peterson (Frontiers in Marine Science, 2015)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Diverse phenotypic consequences of mutations affecting the C-terminus of FLNA - Margriet van Kogelenberg; Alice R. Clark; Zandra Jenkins; Tim Morgan; Ananda Anandan; Gregory M. Sawyer; Matthew Edwards; Tracy Dudding; Tessa Homfray; Bruce Castle; John Tolmie; Fiona Stewart; et al. (Journal of Molecular Medicine, 2015)

A pan‐Arctic synthesis of CH 4 and CO 2 production from anoxic soil incubations - Claire C. Treat; Susan M. Natali; Jessica Ernakovich; Colleen M. Iversen; Massimo Lupascu; Anthony David McGuire; Richard J. Norby; Taniya Roy Chowdhury; Andreas Richter; Hana Šantrůčková; Christina Schädel; Edward A. G. Schuur; et al. (Global Change Biology, 2015)
Permafrost thaw can alter the soil environment through changes in soil moisture, frequently resulting in soil saturation, a shift to anaerobic decomposition, and changes in the plant community. These changes, along with thawing of previously frozen organic material, can alter the form and magnitude of greenhouse gas production from permafrost ecosystems. We synthesized existing methane (CH 4 ) and carbon dioxide (CO 2 ) production measurements from anaerobic incubations of boreal and tundra soils from the geographic permafrost region to evaluate large‐scale controls of anaerobic CO 2 and CH 4 production and compare the relative importance of landscape‐level factors (e.g., vegetation type and landscape position), soil properties (e.g., pH, depth, and soil type), and soil environmental conditions (e.g., temperature and relative water table position). We found fivefold higher maximum CH 4 production per gram soil carbon from organic soils than mineral soils. Maximum CH 4 production from soils in the active layer (ground that thaws and refreezes annually) was nearly four times that of permafrost per gram soil carbon, and CH 4 production per gram soil carbon was two times greater from sites without permafrost than sites with permafrost. Maximum CH 4 and median anaerobic CO 2 production decreased with depth, while CO 2 :CH 4 production increased with depth. Maximum CH 4 production was highest in soils with herbaceous vegetation and soils that were either consistently or periodically inundated. This synthesis identifies the need to consider biome, landscape position, and vascular/moss vegetation types when modeling CH 4 production in permafrost ecosystems and suggests the need for longer‐term anaerobic incubations to fully capture CH 4 dynamics. Our results demonstrate that as climate warms in arctic and boreal regions, rates of anaerobic CO 2 and CH 4 production will increase, not only as a result of increased temperature, but also from shifts in vegetation and increased ground saturation that will accompany permafrost thaw.

Decadal trends of atmospheric methane in East Asia from 1991 to 2013 - Hak-Sung Kim; Yong S. Chung; Pieter P. Tans; Edward J. Dlugokencky (Air Quality, Atmosphere & Health, 2015)

Small Amounts of Sub-Visible Aggregates Enhance the Immunogenic Potential of Monoclonal Antibody Therapeutics - Maryam Ahmadi; Christine J. Bryson; Edward A. Cloake; Katie Welch; Vasco Filipe; Stefan Romeijn; Andrea Hawe; Wim Jiskoot; Matthew P. Baker; Mark H. Fogg (Pharmaceutical Research, 2015)

Minimizing the biodiversity impact of Neotropical oil palm development - James J. Gilroy; Graham W. Prescott; Johann S. Cardenas; Pamela González del Pliego Castañeda; Andrés Sánchez; Luis E. Rojas‐Murcia; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2015)
Oil palm agriculture is rapidly expanding in the Neotropics, at the expense of a range of natural and seminatural habitats. A key question is how this expansion should be managed to reduce negative impacts on biodiversity. Focusing on the Llanos of Colombia, a mixed grassland–forest system identified as a priority zone for future oil palm development, we survey communities of ants, dung beetles, birds and herpetofauna occurring in oil palm plantations and the other principal form of agriculture in the region – improved cattle pasture – together with those of surrounding natural forests. We show that oil palm plantations have similar or higher species richness across all four taxonomic groups than improved pasture. For dung beetles, species richness in oil palm was equal to that of forest, whereas the other three taxa had highest species richness in forests. Hierarchical modelling of species occupancy probabilities indicated that oil palm plantations supported a higher proportion of species characteristic of forests than did cattle pastures. Across the bird community, occupancy probabilities within oil palm were positively influenced by increasing forest cover in a surrounding 250 m radius, whereas surrounding forest cover did not strongly influence the occurrence of other taxonomic groups in oil palm. Overall, our results suggest that the conversion of existing improved pastures to oil palm has limited negative impacts on biodiversity. As such, existing cattle pastures of the Colombian Llanos could offer a key opportunity to meet governmental targets for oil palm development without incurring significant biodiversity costs. Our results also highlight the value of preserving remnant forests within these agricultural landscapes, protecting high biodiversity and exporting avian ‘spill‐over’ effects into oil palm plantations.

Effect of scale on trait predictors of species responses to agriculture - James J. Gilroy; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Conservation Biology, 2015)
Species persistence in human‐altered landscapes can depend on factors operating at multiple spatial scales. To understand anthropogenic impacts on biodiversity, it is useful to examine relationships between species traits and their responses to land‐use change. A key knowledge gap concerns whether these relationships vary depending on the scale of response under consideration. We examined how local‐ and large‐scale habitat variables influence the occupancy dynamics of a bird community in cloud forest zones in the Colombian Chocó‐Andes. Using data collected across a continuum of forest and agriculture, we examined which traits best predict species responses to local variation in farmland and which traits best predict species responses to isolation from contiguous forest. Global range size was a strong predictor of species responses to agriculture at both scales; widespread species were less likely to decline as local habitat cover decreased and as distance from forest increased. Habitat specialization was a strong predictor of species responses only at the local scale. Open‐habitat species were particularly likely to increase as pasture increased, but they were relatively insensitive to variation in distance to forest. Foraging plasticity and flocking behavior were strong predictors of species responses to distance from forest, but not their responses to local habitat. Species with lower plasticity in foraging behaviors and obligate flock‐following species were more likely to decline as distance from contiguous forest increased. For species exhibiting these latter traits, persistence in tropical landscapes may depend on the protection of larger contiguous blocks of forest, rather than the integration of smaller‐scale woodland areas within farmland. Species listed as threatened or near threatened on the International Union for Conservation of Nature Red List were also more likely to decline in response to both local habitat quality and isolation from forest relative to least‐concern species, underlining the importance of contiguous forests for threatened taxa.

Anterior–posterior dissociation of the default mode network in dogs - Sreenath P. Kyathanahally; Hao Jia; Oleg M. Pustovyy; Paul Waggoner; Ronald Beyers; John Schumacher; Jay Barrett; Edward E. Morrison; Nouha Salibi; Thomas S. Denney; Vitaly J. Vodyanoy; Gopikrishna Deshpande (Brain Structure and Function, 2015)

Worldwide phylogeography of the invasive ctenophore Mnemiopsis leidyi (Ctenophora) based on nuclear and mitochondrial DNA data - K. M. Bayha; M. H. Chang; C. L. Mariani; J. L. Richardson; D. L. Edwards; T. S. DeBoer; C. Moseley; E. Aksoy; M. B. Decker; P. M. Gaffney; G. R. Harbison; J. H. McDonald; et al. (Biological Invasions, 2015)

Decadal environmental ‘memory’ in a reef coral? - B. E. Brown; R. P. Dunne; A. J. Edwards; M. J. Sweet; N. Phongsuwan (Marine Biology, 2015)

Behavior in invasive New Zealand mud snails (Potamopyrgus antipodarum) is related to source population - Edward P. Levri; T. J. Clark (Biological Invasions, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Normal Motor Adaptation in Cervical Dystonia: A Fundamental Cerebellar Computation is Intact - Anna Sadnicka; Bansi Patani; Tabish A. Saifee; Panagiotis Kassavetis; Isabel Pareés; Prasad Korlipara; Kailash P. Bhatia; John C. Rothwell; Joseph M. Galea; Mark J. Edwards (The Cerebellum, 2014)

Preface - Human-altered coastal systems: processes, monitoring, and management - Edward J. Anthony; Norbert P. Psuty (Journal of Coastal Conservation, 2014)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Ecosystem-Scale Rates of Primary Production Within Wetland Habitats of the Northern San Francisco Estuary - Risa A. Cohen; Frances P. Wilkerson; Alexander E. Parker; Edward J. Carpenter (Wetlands, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Chronic water stress reduces tree growth and the carbon sink of deciduous hardwood forests - Edward R. Brzostek; Danilo Dragoni; Hans Peter Schmid; Abdullah F. Rahman; Daniel Sims; Craig A. Wayson; Daniel J. Johnson; Richard P. Phillips (Global Change Biology, 2014)
Predicted decreases in water availability across the temperate forest biome have the potential to offset gains in carbon (C) uptake from phenology trends, rising atmospheric CO 2 , and nitrogen deposition. While it is well established that severe droughts reduce the C sink of forests by inducing tree mortality, the impacts of mild but chronic water stress on forest phenology and physiology are largely unknown. We quantified the C consequences of chronic water stress using a 13‐year record of tree growth ( n = 200 trees), soil moisture, and ecosystem C balance at the Morgan–Monroe State Forest ( MMSF ) in Indiana, and a regional 11‐year record of tree growth ( n > 300 000 trees) and water availability for the 20 most dominant deciduous broadleaf tree species across the eastern and midwestern USA . We show that despite ~26 more days of C assimilation by trees at the MMSF , increasing water stress decreased the number of days of wood production by ~42 days over the same period, reducing the annual accrual of C in woody biomass by 41%. Across the deciduous forest region, water stress induced similar declines in tree growth, particularly for water‐demanding ‘mesophytic’ tree species. Given the current replacement of water‐stress adapted ‘xerophytic’ tree species by mesophytic tree species, we estimate that chronic water stress has the potential to decrease the C sink of deciduous forests by up to 17% (0.04 Pg C yr −1 ) in the coming decades. This reduction in the C sink due to mesophication and chronic water stress is equivalent to an additional 1–3 days of global C emissions from fossil fuel burning each year. Collectively, our results indicate that regional declines in water availability may offset the growth‐enhancing effects of other global changes and reduce the extent to which forests ameliorate climate warming.

Tree Response to Experimental Watershed Acidification - N. K. Jensen; E. J. Holzmueller; P. J. Edwards; M. Thomas-Van Gundy; D. R. DeWalle; K. W. J. Williard (Water, Air, & Soil Pollution, 2014)

Genetic control of grain yield and grain physical characteristics in a bread wheat population grown under a range of environmental conditions - Lancelot Maphosa; Peter Langridge; Helen Taylor; Boris Parent; Livinus C. Emebiri; Haydn Kuchel; Matthew P. Reynolds; Ken J. Chalmers; Anzu Okada; James Edwards; Diane E. Mather (Theoretical and Applied Genetics, 2014)

Enhancement of the accuracy of single-epoch GPS positioning for long baselines by local ionospheric modelling - M. Assiadi; S. J. Edwards; P. J. Clarke (GPS Solutions, 2014)

Optimizing carbon storage and biodiversity protection in tropical agricultural landscapes - James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Charlotte Wheeler; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2014)
With the rapidly expanding ecological footprint of agriculture, the design of farmed landscapes will play an increasingly important role for both carbon storage and biodiversity protection. Carbon and biodiversity can be enhanced by integrating natural habitats into agricultural lands, but a key question is whether benefits are maximized by including many small features throughout the landscape (‘land‐sharing’ agriculture) or a few large contiguous blocks alongside intensive farmland (‘land‐sparing’ agriculture). In this study, we are the first to integrate carbon storage alongside multi‐taxa biodiversity assessments to compare land‐sparing and land‐sharing frameworks. We do so by sampling carbon stocks and biodiversity (birds and dung beetles) in landscapes containing agriculture and forest within the Colombian Chocó‐Andes, a zone of high global conservation priority. We show that woodland fragments embedded within a matrix of cattle pasture hold less carbon per unit area than contiguous primary or advanced secondary forests (>15 years). Farmland sites also support less diverse bird and dung beetle communities than contiguous forests, even when farmland retains high levels of woodland habitat cover. Landscape simulations based on these data suggest that land‐sparing strategies would be more beneficial for both carbon storage and biodiversity than land‐sharing strategies across a range of production levels. Biodiversity benefits of land‐sparing are predicted to be similar whether spared lands protect primary or advanced secondary forests, owing to the close similarity of bird and dung beetle communities between the two forest classes. Land‐sparing schemes that encourage the protection and regeneration of natural forest blocks thus provide a synergy between carbon and biodiversity conservation, and represent a promising strategy for reducing the negative impacts of agriculture on tropical ecosystems. However, further studies examining a wider range of ecosystem services will be necessary to fully understand the links between land‐allocation strategies and long‐term ecosystem service provision.

Erratum to: A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

A genome-wide association study of prostate cancer in West African men - Michael Blaise Cook; Zhaoming Wang; Edward D. Yeboah; Yao Tettey; Richard B. Biritwum; Andrew A. Adjei; Evelyn Tay; Ann Truelove; Shelley Niwa; Charles C. Chung; Annand P. Chokkalingam; Lisa W. Chu; et al. (Human Genetics, 2014)

Current Challenges in Bioequivalence, Quality, and Novel Assessment Technologies for Topical Products - Avraham Yacobi; Vinod P. Shah; Edward D. Bashaw; Eva Benfeldt; Barbara Davit; Derek Ganes; Tapash Ghosh; Isadore Kanfer; Gerald B. Kasting; Lindsey Katz; Robert Lionberger; Guang Wei Lu; et al. (Pharmaceutical Research, 2014)

Normal eyeblink classical conditioning in patients with fixed dystonia - Sabine Janssen; Lidwien C. Veugen; Britt S. Hoffland; Panagiotis Kassavetis; Diana E. van Rooijen; Dick F. Stegeman; Mark J. Edwards; Jacobus J. van Hilten; Bart P. van de Warrenburg (Experimental Brain Research, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Non-invasive Cerebellar Stimulation—a Consensus Paper - G. Grimaldi; G. P. Argyropoulos; A. Boehringer; P. Celnik; M. J. Edwards; R. Ferrucci; J. M. Galea; S. J. Groiss; K. Hiraoka; P. Kassavetis; E. Lesage; M. Manto; et al. (The Cerebellum, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Modeled diversity effects on microbial ecosystem functions of primary production, nutrient uptake, and remineralization - Nicole L. Goebel; Christopher A. Edwards; Michael J. Follows; Jonathan P. Zehr (Ecology, 2014)
Ecosystem‐wide primary productivity generally increases with primary producer diversity, emphasizing the importance of diversity for ecosystem function. However, most studies that demonstrate this positive relationship have focused on terrestrial and aquatic benthic systems, with little attention to the diverse marine pelagic primary producers that play an important role in regulating global climate. Here we show how phytoplankton biodiversity enhances overall marine ecosystem primary productivity and other ecosystem functions using a self‐organizing ecosystem model. Diversity manipulation numerical experiments reveal positive, asymptotically saturating relationships between ecosystem‐wide phytoplankton diversity and functions of productivity, nutrient uptake, remineralization, and diversity metrics used to identify mechanisms shaping these relationships. Increase in productivity with increasing diversity improves modeled ecosystem stability and model robustness and leads to productivity rates that exceed expected yields primarily through niche complementarity and facilitative interactions between coexisting phytoplankton types; the composition of traits in assemblages determines the magnitude of complementarity and selection effects. While findings based on these aggregate measures of diversity effects parallel those from the majority of experimental outcomes of terrestrial and benthic biodiversity–ecosystem function studies, we combine analyses of community diversity effects and investigations of the underlying interactions among phytoplankton types to demonstrate how an increase in recycled production of non‐diatoms through an increase in new production of diatoms drives this diversity–ecosystem function response. We demonstrate the important role that facilitation plays in the modeled marine plankton and how this facilitative interaction could amplify future climate‐driven changes in ocean ecosystem productivity.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Rht-1 and Ppd-D1 associations with height, GA sensitivity, and days to heading in a worldwide bread wheat collection - Edward P. Wilhelm; Margaret I. Boulton; Nadia Al-Kaff; Francois Balfourier; Jacques Bordes; Andy J. Greenland; Wayne Powell; Ian J. Mackay (Theoretical and Applied Genetics, 2013)

A de novo FLCN mutation in a patient with spontaneous pneumothorax and renal cancer; a clinical and molecular evaluation - Fred H. Menko; Paul C. Johannesma; R. Jeroen A. van Moorselaar; Rinze Reinhard; Jan Hein van Waesberghe; Erik Thunnissen; Arjan C. Houweling; Edward M. Leter; Quinten Waisfisz; Martijn B. van Doorn; Theo M. Starink; Pieter E. Postmus; et al. (Familial Cancer, 2013)

On the influence of tree size on the climate–growth relationship of New Zealand kauri (Agathis australis): insights from annual, monthly and daily growth patterns - Jan Wunder; Anthony M. Fowler; Edward R. Cook; Maryann Pirie; Shane P. J. McCloskey (Trees, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Haplotype dictionary for the Rht-1 loci in wheat - Edward P. Wilhelm; Ian J. Mackay; Robert J. Saville; Andrey V. Korolev; Francois Balfourier; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Immunohistochemical localization of urea and ammonia transporters in two confamilial fish species, the ureotelic gulf toadfish (Opsanus beta) and the ammoniotelic plainfin midshipman (Porichthys notatus) - Carol Bucking; Susan L. Edwards; Paul Tickle; Craig P. Smith; M. Danielle McDonald; Patrick J. Walsh (Cell and Tissue Research, 2013)

Genetic characterization and mapping of the Rht-1 homoeologs and flanking sequences in wheat - Edward P. Wilhelm; Rhian M. Howells; Nadia Al-Kaff; Jizeng Jia; Catherine Baker; Michelle A. Leverington-Waite; Simon Griffiths; Andy J. Greenland; Margaret I. Boulton; Wayne Powell (Theoretical and Applied Genetics, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Building the niche through time: using 13,000 years of data to predict the effects of climate change on three tree species in Europe - L. Maiorano; R. Cheddadi; N. E. Zimmermann; L. Pellissier; B. Petitpierre; J. Pottier; H. Laborde; B. I. Hurdu; P. B. Pearman; A. Psomas; J. S. Singarayer; O. Broennimann; et al. (Global Ecology and Biogeography, 2013)
Aim Species distribution models (SDMs) based on current species ranges underestimate the potential distribution when projected in time and/or space. A multi‐temporal model calibration approach has been suggested as an alternative, and we evaluate this using 13,000 years of data. Location Europe. Methods We used fossil‐based records of presence for Picea abies , Abies alba and Fagus sylvatica and six climatic variables for the period 13,000 to 1000 yr bp . To measure the contribution of each 1000‐year time step to the total niche of each species (the niche measured by pooling all the data), we employed a principal components analysis (PCA) calibrated with data over the entire range of possible climates. Then we projected both the total niche and the partial niches from single time frames into the PCA space, and tested if the partial niches were more similar to the total niche than random. Using an ensemble forecasting approach, we calibrated SDMs for each time frame and for the pooled database. We projected each model to current climate and evaluated the results against current pollen data. We also projected all models into the future. Results Niche similarity between the partial and the total‐SDMs was almost always statistically significant and increased through time. SDMs calibrated from single time frames gave different results when projected to current climate, providing evidence of a change in the species realized niches through time. Moreover, they predicted limited climate suitability when compared with the total‐SDMs. The same results were obtained when projected to future climates. Main conclusions The realized climatic niche of species differed for current and future climates when SDMs were calibrated considering different past climates. Building the niche as an ensemble through time represents a way forward to a better understanding of a species' range and its ecology in a changing climate.

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Effects of mu opioid receptor antagonism on cognition in obese binge-eating individuals - Samuel R. Chamberlain; Karin Mogg; Brendan P. Bradley; Annelize Koch; Chris M. Dodds; Wenli X. Tao; Kay Maltby; Bhopinder Sarai; Antonella Napolitano; Duncan B. Richards; Edward T. Bullmore; Pradeep J. Nathan (Psychopharmacology, 2012)

Long-term development of a cultural landscape: the origins and dynamics of lowland heathland in southern England - Jon A. Groves; Martyn P. Waller; Michael J. Grant; J. Edward Schofield (Vegetation History and Archaeobotany, 2012)

Phylogenetic niche conservatism in C4 grasses - Hui Liu; Erika J. Edwards; Robert P. Freckleton; Colin P. Osborne (Oecologia, 2012)

Adaptation of surround inhibition in the human motor system - P. Kassavetis; T. A. Saifee; A. Sadnicka; I. Pareés; M. Kojovic; J. C. Rothwell; M. J. Edwards (Experimental Brain Research, 2012)

Assimilating GlobColour ocean colour data into a pre-operational physical-biogeochemical model - D. A. Ford; K. P. Edwards; D. Lea; R. M. Barciela; M. J. Martin; J. Demaria (Ocean Science, 2012)
As part of the GlobColour project, daily chlorophyll a observations, derived using remotely sensed ocean colour data from the MERIS, MODIS and SeaWiFS sensors, are produced. The ability of these products to be assimilated into a pre-operational global coupled physical-biogeochemical model has been tested, on both a hindcast and near-real-time basis, and the impact on the system assessed. The assimilation was found to immediately and considerably improve the bias, root mean square error and correlation of modelled surface chlorophyll concentration compared to the GlobColour observations, an improvement which was sustained throughout the year and in every ocean basin. Errors against independent in situ chlorophyll observations were also reduced, both at and beneath the ocean surface. However, the model fit to in situ observations was not consistently better than that of climatology, due to errors in the underlying model. The assimilation scheme used is multivariate, updating all biogeochemical model state variables at all depths. The other variables were not degraded by the assimilation, with annual mean surface fields of nutrients, alkalinity and carbon variables remaining of similar quality compared to climatology. There was evidence of improved representation of zooplankton concentration, and reduced errors were seen against in situ observations of nitrate and pCO2, but too few observations were available to conclude about global model skill. The near-real-time GlobColour products were found to be sufficiently reliable for operational purposes, and of benefit to both operational-style systems and reanalyses.

The Gauss–Listing geopotential value W 0 and its rate from altimetric mean sea level and GRACE - N. Dayoub; S. J. Edwards; P. Moore (Journal of Geodesy, 2012)

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

Assessing trophic position from nitrogen isotope ratios: effective calibration against spatially varying baselines - Paul Woodcock; David P. Edwards; Rob J. Newton; Felicity A. Edwards; Chey Vun Khen; Simon H. Bottrell; Keith C. Hamer (The Science of Nature, 2012)

Transcriptomic alterations induced by Ochratoxin A in rat and human renal proximal tubular in vitro models and comparison to a rat in vivo model - Paul Jennings; Christina Weiland; Alice Limonciel; Katarzyna M. Bloch; Robert Radford; Lydia Aschauer; Tara McMorrow; Anja Wilmes; Walter Pfaller; Hans J. Ahr; Craig Slattery; Edward A. Lock; et al. (Archives of Toxicology, 2012)

Concentrated flow paths in riparian buffer zones of southern Illinois - R. C. Pankau; J. E. Schoonover; K. W. J. Williard; P. J. Edwards (Agroforestry Systems, 2012)

Hybridisation of Australian chickpea cultivars with wild Cicer spp. increases resistance to root-lesion nematodes (Pratylenchus thornei and P. neglectus) - John P. Thompson; Roslyn A. Reen; Timothy G. Clewett; Jason G. Sheedy; Alison M. Kelly; Beverley J. Gogel; Edward J. Knights (Australasian Plant Pathology, 2011)

High frequency variability of the Atlantic meridional overturning circulation - B. Balan Sarojini; J. M. Gregory; R. Tailleux; G. R. Bigg; A. T. Blaker; D. R. Cameron; N. R. Edwards; A. P. Megann; L. C. Shaffrey; B. Sinha (Ocean Science, 2011)
We compare the variability of the Atlantic meridional overturning circulation (AMOC) as simulated by the coupled climate models of the RAPID project, which cover a wide range of resolution and complexity, and observed by the RAPID/MOCHA array at about 26° N. We analyse variability on a range of timescales, from five-daily to interannual. In models of all resolutions there is substantial variability on timescales of a few days; in most AOGCMs the amplitude of the variability is of somewhat larger magnitude than that observed by the RAPID array, while the time-mean is within about 10 % of the observational estimate. The amplitude of the simulated annual cycle is similar to observations, but the shape of the annual cycle shows a spread among the models. A dynamical decomposition shows that in the models, as in observations, the AMOC is predominantly geostrophic (driven by pressure and sea-level gradients), with both geostrophic and Ekman contributions to variability, the latter being exaggerated and the former underrepresented in models. Other ageostrophic terms, neglected in the observational estimate, are small but not negligible. The time-mean of the western boundary current near the latitude of the RAPID/MOCHA array has a much wider model spread than the AMOC does, indicating large differences among models in the simulation of the wind-driven gyre circulation, and its variability is unrealistically small in the models. In many RAPID models and in models of the Coupled Model Intercomparison Project Phase 3 (CMIP3), interannual variability of the maximum of the AMOC wherever it lies, which is a commonly used model index, is similar to interannual variability in the AMOC at 26° N. Annual volume and heat transport timeseries at the same latitude are well-correlated within 15–45° N, indicating the climatic importance of the AMOC. In the RAPID and CMIP3 models, we show that the AMOC is correlated over considerable distances in latitude, but not the whole extent of the North Atlantic; consequently interannual variability of the AMOC at 50° N, where it is particularly relevant to European climate, is not well-correlated with that of the AMOC at 26° N, where it is monitored by the RAPID/MOCHA array.

The Mid‐Brunhes Event and West Antarctic ice sheet stability - P. B. Holden; N. R. Edwards; E. W. Wolff; P. J. Valdes; J. S. Singarayer (Journal of Quaternary Science, 2011)
The complex cyclical nature of Pleistocene climate, driven by the evolving orbital configuration of the Earth, is well known but not well understood. A major climatic transition took place at the Mid‐Brunhes Event (MBE), ca. 430 ka ago after which the amplitude of the ca.100 ka climate oscillations increased, with substantially warmer interglacials, including periods warmer than present. Recent modelling has indicated that while the timing of these warmer‐than‐present transient (WPT) events is consistent with southern warming due to a deglaciation‐forced slowdown of the Atlantic Meridional Overturning Circulation, the magnitude of warming requires a local amplification, for which a candidate is the feedback of significant West Antarctic Ice Sheet (WAIS) retreat. We here extend this argument, based on the absence of WPTs in the early ice core record (450–800 ka ago), to hypothesize that the MBE could be a manifestation of decreased WAIS stability, triggered by ongoing subglacial erosion. Copyright © 2011 John Wiley & Sons, Ltd.

High Performance Thin Layer Chromatography (HPTLC) profile of an insecticidal compound of Trochus radiatus and assessment of mucus-associated bacterial extracts - Mary Elizabeth K. Gnanambal; K. C. Ramya Devi; P. Hareesh Chandra; Edward J. K. Patterson (Phytoparasitica, 2011)

Motivation and movement: the effect of monetary incentive on performance speed - Pablo Mir; Iris Trender-Gerhard; Mark J. Edwards; Susanne A. Schneider; Kailash P. Bhatia; Marjan Jahanshahi (Experimental Brain Research, 2011)

Cerebellar brain inhibition is decreased in active and surround muscles at the onset of voluntary movement - Panagiotis Kassavetis; Britt S. Hoffland; Tabish A. Saifee; Kailash P. Bhatia; Bart P. van de Warrenburg; John C. Rothwell; Mark J. Edwards (Experimental Brain Research, 2011)

Monitoring seasonal bat activity on a coastal barrier island in Maryland, USA - Joshua B. Johnson; J. Edward Gates; Nicolas P. Zegre (Environmental Monitoring and Assessment, 2011)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

The influence of interval versus continuous exercise on thermoregulation, torso hemodynamics, and finger dexterity in the cold - Matthew D. Muller; Edward J. Ryan; David M. Bellar; Chul-Ho Kim; Robert P. Blankfield; Sarah M. Muller; Ellen L. Glickman (European Journal of Applied Physiology, 2010)

Negative soil feedbacks accumulate over time for non‐native plant species - Jeffrey M. Diez; Ian Dickie; Grant Edwards; Philip E. Hulme; Jon J. Sullivan; Richard P. Duncan (Ecology Letters, 2010)
Ecology Letters (2010) 13: 803–809 Abstract The enemy release hypothesis is a common explanation for species invasions, suggesting that introduced species benefit from leaving behind natural enemies in the native range. However, any such advantage may attenuate over time. In this study, we test a prediction of this more dynamic enemy release hypothesis: that non‐native plant species that became established longer ago exhibit stronger negative feedbacks with the soil. Consistent with declining enemy release over time, we found increasingly negative soil feedbacks for species established longer ago in New Zealand. Negative soil feedbacks were also stronger for more widespread species, but weaker for more locally abundant species, suggesting that species accumulate negative interactions as they spread and can be locally regulated by these interactions. We also present data to support the common assumption that relatives have similar impacts on and responses to soil communities. Together, these data highlight the dynamic nature of novel interactions arising from species introductions.

The Role of the Intestinal Lymphatics in the Absorption of Two Highly Lipophilic Cholesterol Ester Transfer Protein Inhibitors (CP524,515 and CP532,623) - Natalie L. Trevaskis; Claire L. McEvoy; Michelle P. McIntosh; Glenn A. Edwards; Ravi M. Shanker; William N. Charman; Christopher J. H. Porter (Pharmaceutical Research, 2010)

Derivation and characterisation of the human embryonic stem cell line, OxF1 - Frances Anne Brook; Sally A. Cowley; Edward P. Evans; Karen Turner; William S. James; Helen J. Mardon (In Vitro Cellular & Developmental Biology - Animal, 2010)

The high value of logged tropical forests: lessons from northern Borneo - Nicholas J. Berry; Oliver L. Phillips; Simon L. Lewis; Jane K. Hill; David P. Edwards; Noel B. Tawatao; Norhayati Ahmad; David Magintan; Chey V. Khen; M. Maryati; Robert C. Ong; Keith C. Hamer (Biodiversity and Conservation, 2010)

Effects of seagrasses and algae of the Caulerpa family on hydrodynamics and particle-trapping rates - Iris E. Hendriks; Tjeerd J. Bouma; Edward P. Morris; Carlos M. Duarte (Marine Biology, 2010)

Comparing plasma and faecal measures of steroid hormones in Adelie penguins Pygoscelis adeliae - Calum Edward Ninnes; J. R. Waas; N. Ling; S. Nakagawa; J. C. Banks; D. G. Bell; A. Bright; P. W. Carey; J. Chandler; Q. J. Hudson; J. R. Ingram; K. Lyall; et al. (Journal of Comparative Physiology B, 2010)

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

Reproducibility between counts of airborne allergenic pollen from two cities in the East Midlands, UK - Catherine H. Pashley; Abbie Fairs; Richard E. Edwards; John P. Bailey; Julie M. Corden; Andrew J. Wardlaw (Aerobiologia, 2009)

Acid soil indicators in forest soils of the Cherry River Watershed, West Virginia - C. Farr; J. Skousen; P. Edwards; S. Connolly; J. Sencindiver (Environmental Monitoring and Assessment, 2009)

Rapid effects of hypoxia on H+ homeostasis in articular chondrocytes - John S. Gibson; David McCartney; Joanna Sumpter; Thomas P. A. Fairfax; Peter I. Milner; Hannah L. Edwards; Robert J. Wilkins (Pflügers Archiv - European Journal of Physiology, 2009)

Linking stream and landscape trajectories in the southern Appalachians - Edward P. Gardiner; Andrew B. Sutherland; Rebecca J. Bixby; Mark C. Scott; Judy L. Meyer; Gene S. Helfman; E. Fred Benfield; Cathy M. Pringle; Paul V. Bolstad; David N. Wear (Environmental Monitoring and Assessment, 2009)

Adaptive response of equine intestinal Na+/glucose co-transporter (SGLT1) to an increase in dietary soluble carbohydrate - Jane Dyer; Miran Al-Rammahi; Louise Waterfall; Kieron S. H. Salmon; Ray J. Geor; Ludovic Bouré; G. Barrie Edwards; Christopher J. Proudman; Soraya P. Shirazi-Beechey (Pflügers Archiv - European Journal of Physiology, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Forward and reverse genetics of rapid-cycling Brassica oleracea - Edward Himelblau; Erin J. Gilchrist; Kelly Buono; Colleen Bizzell; Laurie Mentzer; Robert Vogelzang; Thomas Osborn; Richard M. Amasino; Isobel A. P. Parkin; George W. Haughn (Theoretical and Applied Genetics, 2009)

The diversity and abundance of bacteria inhabiting seafloor lavas positively correlate with rock alteration - Cara M. Santelli; Virginia P. Edgcomb; Wolfgang Bach; Katrina J. Edwards (Environmental Microbiology, 2009)
Summary Young, basaltic ocean crust exposed near mid‐ocean ridge spreading centers present a spatially extensive environment that may be exploited by epi‐ and endolithic microbes in the deep sea. Geochemical energy released during basalt alteration reactions can theoretically support chemosynthesis, contributing to a trophic base for the ocean crust biome. To examine associations between endolithic microorganisms and basalt alteration processes, we compare the phylogenetic diversity, abundance and community structure of bacteria existing in several young, seafloor lavas from the East Pacific Rise at ∼9°N that are variably affected by oxidative seawater alteration. The results of 16S rRNA gene analyses and real‐time, quantitative polymerase chain reaction measurements show that the abundance of prokaryotic communities, dominated by the bacterial domain, positively correlates with the extent of rock alteration – the oldest, most altered basalt harbours the greatest microbial biomass. The bacterial community overlap, structure and species richness relative to alteration state is less explicit, but broadly corresponds to sample characteristics (type of alteration products and general alteration state). Phylogenetic analyses suggest that the basalt biome may contribute to the geochemical cycling of Fe, S, Mn, C and N in the deep sea.

Relationship Between Pink Eye Symptoms and Cell Damage in the Tuber Periderm and Cortex - Robert P. Sabba; Alvin J. Bussan; Edward C. Lulai (American Journal of Potato Research, 2008)

Sub‐millennial climate shifts in the western Mediterranean during the last glacial period recorded in a speleothem from Mallorca, Spain - Edward J. Hodge; David A. Richards; Peter L. Smart; Angel Ginés; David P. Mattey (Journal of Quaternary Science, 2008)
Very few high‐resolution and directly dated terrestrial archives of the last glacial period exist for the western Mediterranean region, yet this is a key locality for recording sub‐millennial North Atlantic and Mediterranean climate change. Here, we present evidence of effective precipitation changes based on growth history and δ 13 C of calcite in a Mallorcan stalagmite that grew between 112 and 48 ka. Effective precipitation in Mallorca appears to have been sensitive to proximal sea surface temperature variations and at certain times, ca. 76 ka for example, changed rapidly from moist to arid conditions in only a few centuries. A sea‐level highstand during Marine Isotope Stage (MIS) 5a interrupted growth. Regrowth started promptly after this, but effective precipitation decreased markedly for much of the later part of MIS 5a, and also for shorter periods correlative with Heinrich events H8 (ca. 90 ka) and H6 (ca. 65 ka), with growth ceasing during H5 (ca. 48 ka). Arid episodes in Mallorca appear to be expressions of extremely cold periods recorded further north in Europe and occur contemporaneously with rapid decreases in Greenland temperature. Copyright © 2008 John Wiley & Sons, Ltd.

Cell-type-specific level of DNA nucleotide excision repair in primary human mammary and ovarian epithelial cell cultures - Jean J. Latimer; Jennifer M. Johnson; Tiffany D. Miles; Jason M. Dimsdale; Robert P. Edwards; Joseph L. Kelley; Stephen G. Grant (Cell and Tissue Research, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Dispersal of black sea bass ( Centropristis striata ) larvae on the southeast U.S. continental shelf: results of a coupled vertical larval behavior – 3D circulation model - K. P. EDWARDS; J. A. HARE; F. E. WERNER (Fisheries Oceanography, 2008)
In the marine environment, pelagic dispersal is important for determining the distribution and abundance of populations, as well as providing connections among populations. Estimates of larval dispersal from spawning grounds are important to determining temporal and spatial patterns in recruitment that may have significant influences on the dynamics of the population. We present a case study of the dispersal of Centropristis striata (black sea bass) larvae on the southeast U.S. continental shelf. We use a coupled larval behavior – 3D circulation model to compare the effects of the timing and location of spawning against that of larval vertical migration on larval dispersal. Using the results of field data on larval vertical distributions, we compare the dispersal of virtual ‘larvae’ which have ontogenetic changes in vertical behavior with that of particles fixed near the surface and near the bottom. Larvae were released at potential spawning sites four times throughout the spawning season (February through May) for 3 yr (2002–04) and tracked for the assumed larval duration (from 27 to 37 days including the egg stage). Results indicate that adult behavior, in the form of spawning time and location, may be more important than larval vertical behavior in determining larval dispersal on the inner‐ and mid‐ continental shelves of this region.

Darwin’s naturalization conundrum: dissecting taxonomic patterns of species invasions - Jeffrey M. Diez; Jon J. Sullivan; Philip E. Hulme; Grant Edwards; Richard P. Duncan (Ecology Letters, 2008)
Darwin acknowledged contrasting, plausible arguments for how species invasions are influenced by phylogenetic relatedness to the native community. These contrasting arguments persist today without clear resolution. Using data on the naturalization and abundance of exotic plants in the Auckland region, we show how different expectations can be accommodated through attention to scale, assumptions about niche overlap, and stage of invasion. Probability of naturalization was positively related to the number of native species in a genus but negatively related to native congener abundance, suggesting the importance of both niche availability and biotic resistance. Once naturalized, however, exotic abundance was not related to the number of native congeners, but positively related to native congener abundance. Changing the scale of analysis altered this outcome: within habitats exotic abundance was negatively related to native congener abundance, implying that native and exotic species respond similarly to broad scale environmental variation across habitats, with biotic resistance occurring within habitats.

Dynamics of T cell memory in human cytomegalovirus infection - Edward C. P. Waller; Elizabeth Day; J. G. Patrick Sissons; Mark R. Wills (Medical Microbiology and Immunology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Multi-species spawning of corals in north-western Philippines - K. C. Vicentuan; J. R. Guest; M. V. Baria; P. C. Cabaitan; R. M. Dizon; R. D. Villanueva; P. M. Aliño; A. J. Edwards; E. D. Gomez; A. J. Heyward (Coral Reefs, 2008)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Atlantic reef fish biogeography and evolution - S. R. Floeter; L. A. Rocha; D. R. Robertson; J. C. Joyeux; W. F. Smith‐Vaniz; P. Wirtz; A. J. Edwards; J. P. Barreiros; C. E. L. Ferreira; J. L. Gasparini; A. Brito; J. M. Falcón; et al. (Journal of Biogeography, 2008)
Aim To understand why and when areas of endemism (provinces) of the tropical Atlantic Ocean were formed, how they relate to each other, and what processes have contributed to faunal enrichment. Location Atlantic Ocean. Methods The distributions of 2605 species of reef fishes were compiled for 25 areas of the Atlantic and southern Africa. Maximum‐parsimony and distance analyses were employed to investigate biogeographical relationships among those areas. A collection of 26 phylogenies of various Atlantic reef fish taxa was used to assess patterns of origin and diversification relative to evolutionary scenarios based on spatio‐temporal sequences of species splitting produced by geological and palaeoceanographic events. We present data on faunal (species and genera) richness, endemism patterns, diversity buildup (i.e. speciation processes), and evaluate the operation of the main biogeographical barriers and/or filters. Results Phylogenetic (proportion of sister species) and distributional (number of shared species) patterns are generally concordant with recognized biogeographical provinces in the Atlantic. The highly uneven distribution of species in certain genera appears to be related to their origin, with highest species richness in areas with the greatest phylogenetic depth. Diversity buildup in Atlantic reef fishes involved (1) diversification within each province, (2) isolation as a result of biogeographical barriers, and (3) stochastic accretion by means of dispersal between provinces. The timing of divergence events is not concordant among taxonomic groups. The three soft (non‐terrestrial) inter‐regional barriers (mid‐Atlantic, Amazon, and Benguela) clearly act as ‘filters’ by restricting dispersal but at the same time allowing occasional crossings that apparently lead to the establishment of new populations and species. Fluctuations in the effectiveness of the filters, combined with ecological differences among provinces, apparently provide a mechanism for much of the recent diversification of reef fishes in the Atlantic. Main conclusions Our data set indicates that both historical events (e.g. Tethys closure) and relatively recent dispersal (with or without further speciation) have had a strong influence on Atlantic tropical marine biodiversity and have contributed to the biogeographical patterns we observe today; however, examples of the latter process outnumber those of the former.

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Effects of atmospheric dynamics and ocean resolution on bi-stability of the thermohaline circulation examined using the Grid ENabled Integrated Earth system modelling (GENIE) framework - T. M. Lenton; R. Marsh; A. R. Price; D. J. Lunt; Y. Aksenov; J. D. Annan; T. Cooper-Chadwick; S. J. Cox; N. R. Edwards; S. Goswami; J. C. Hargreaves; P. P. Harris; et al. (Climate Dynamics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Exploration of Ellsworth Subglacial Lake: a concept paper on the development, organisation and execution of an experiment to explore, measure and sample the environment of a West Antarctic subglacial lake - M.J. Siegert; A. Behar; M. Bentley; D. Blake; S. Bowden; P. Christoffersen; C. Cockell; H. Corr; D. C. Cullen; H. Edwards; A. Ellery; C. Ellis-Evans; et al. (Reviews in Environmental Science and Bio/Technology, 2007)

A note on the top-down and bottom-up gradient functions over a forested site - Weiguo Wang; Kenneth J. Davis; Chuixiang Yi; Edward G. Patton; Martha P. Butler; Daniel M. Ricciuto; Peter S. Bakwin (Boundary-Layer Meteorology, 2007)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Just Add Water and the Colorado River Still Reaches the Sea - Edward P. Glenn; Karl W. Flessa; Michael J. Cohen; Pamela L. Nagler; Kirsten Rowell; Francisco Zamora-Arroyo (Environmental Management, 2007)

Mid to late Holocene vegetation and land use history in the Weald of south-eastern England: multiple pollen profiles from the Rye area - Martyn P. Waller; J. Edward Schofield (Vegetation History and Archaeobotany, 2007)

Phylogeography of the high alpine plant Senecio halleri (Asteraceae) in the European Alps: in situ glacial survival with postglacial stepwise dispersal into peripheral areas - O. BETTIN; C. CORNEJO; P. J. EDWARDS; R. HOLDEREGGER (Molecular Ecology, 2007)
Whether alpine plant species survived Pleistocene glaciations in situ on high alpine nunatak mountains is still under debate. To test this hypothesis, Senecio halleri , a high alpine and endemic species with a narrow distribution range in the European Alps, was chosen as a model organism. Polymerase chain reaction‐restriction fragment length polymorphisms of chloroplast DNA (cpDNA PCR‐RFLPs) were used in a phylogeographic analysis of 14 populations of S. halleri , covering its total distribution area. The results of haplotype diversity and distribution gave evidence of in situ glacial survival on siliceous central‐alpine nunatak mountains in two areas, southwest and northeast of the Aosta valley. According to the absence of genetic differentiation between these two nunatak areas (based on amova ), nested clade analysis implied a history of preglacial gene flow, in situ survival and extinction of intermediate populations during glaciation and postglacial stepwise recolonization of peripheral and intermediate areas.

AAPS-FDA Workshop White Paper: Microdialysis Principles, Application and Regulatory Perspectives - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (Pharmaceutical Research, 2007)

GPS sidereal filtering: coordinate- and carrier-phase-level strategies - A. E. Ragheb; P. J. Clarke; S. J. Edwards (Journal of Geodesy, 2007)

AAPS-FDA workshop white paper: Microdialysis principles, application, and regulatory perspectives report from the Joint AAPS-FDA Workshop, November 4–5, 2005, Nashville, TN - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (The AAPS Journal, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Bottom‐up forcing and the decline of Steller sea lions ( Eumetopias jubatus ) in Alaska: assessing the ocean climate hypothesis - ANDREW W. TRITES; ARTHUR J. MILLER; HERBERT D. G. MASCHNER; MICHAEL A. ALEXANDER; STEVEN J. BOGRAD; JOHN A. CALDER; ANTONIETTA CAPOTONDI; KENNETH O. COYLE; EMANUELE DI LORENZO; BRUCE P. FINNEY; EDWARD J. GREGR; CHESTER E. GROSCH; et al. (Fisheries Oceanography, 2007)
Declines of Steller sea lion ( Eumetopias jubatus ) populations in the Aleutian Islands and Gulf of Alaska could be a consequence of physical oceanographic changes associated with the 1976–77 climate regime shift. Changes in ocean climate are hypothesized to have affected the quantity, quality, and accessibility of prey, which in turn may have affected the rates of birth and death of sea lions. Recent studies of the spatial and temporal variations in the ocean climate system of the North Pacific support this hypothesis. Ocean climate changes appear to have created adaptive opportunities for various species that are preyed upon by Steller sea lions at mid‐trophic levels. The east–west asymmetry of the oceanic response to climate forcing after 1976–77 is consistent with both the temporal aspect (populations decreased after the late 1970s) and the spatial aspect of the decline (western, but not eastern, sea lion populations decreased). These broad‐scale climate variations appear to be modulated by regionally sensitive biogeographic structures along the Aleutian Islands and Gulf of Alaska, which include a transition point from coastal to open‐ocean conditions at Samalga Pass westward along the Aleutian Islands. These transition points delineate distinct clusterings of different combinations of prey species, which are in turn correlated with differential population sizes and trajectories of Steller sea lions. Archaeological records spanning 4000 yr further indicate that sea lion populations have experienced major shifts in abundance in the past. Shifts in ocean climate are the most parsimonious underlying explanation for the broad suite of ecosystem changes that have been observed in the North Pacific Ocean in recent decades.

Pink eye is an unusual periderm disorder characterized by aberrant suberization: A cytological analysis - Edward C. Lulai; John J. Weiland; Jeffrey C. Suttle; Robert P. Sabba; A. J. Bussan (American Journal of Potato Research, 2006)

Gap size and succession in cutover southern Appalachian forests: an 18 year study of vegetation dynamics - Donald J. Shure; Donald L. Phillips; P. Edward Bostick (Plant Ecology, 2006)

Pharmacodynamics of Antiretroviral Agents in HIV-1 Infected Patients: Using Viral Dynamic Models that Incorporate Drug Susceptibility and Adherence - Hulin Wu; Yangxin Huang; Edward P. Acosta; Jeong -Gun Park; Song Yu; Susan L. Rosenkranz; Daniel R. Kuritzkes; Joseph J. Eron; Alan S. Perelson; John G. Gerber (Journal of Pharmacokinetics and Pharmacodynamics, 2006)

Sensitivity of Marine‐Reserve Design to the Spatial Resolution of Socioeconomic Data - ELIZABETH A. RICHARDSON; MICHEL J. KAISER; GARETH EDWARDS‐JONES; HUGH P. POSSINGHAM (Conservation Biology, 2006)
Socioeconomic considerations should have an important place in reserve design. Systematic reserve‐selection tools allow simultaneous optimization for ecological objectives while minimizing costs but are seldom used to incorporate socioeconomic costs in the reserve‐design process. The sensitivity of this process to biodiversity data resolution has been studied widely but the issue of socioeconomic data resolution has not previously been considered. We therefore designed marine reserves for biodiversity conservation with the constraint of minimizing commercial fishing revenue losses and investigated how economic data resolution affected the results. Incorporating coarse‐resolution economic data from official statistics generated reserves that were only marginally less costly to the fishery than those designed with no attempt to minimize economic impacts. An intensive survey yielded fine‐resolution data that, when incorporated in the design process, substantially reduced predicted fishery losses. Such an approach could help minimize fisher displacement because the least profitable grounds are selected for the reserve. Other work has shown that low‐resolution biodiversity data can lead to underestimation of the conservation value of some sites, and a risk of overlooking the most valuable areas, and we have similarly shown that low‐resolution economic data can cause underestimation of the profitability of some sites and a risk of inadvertently including these in the reserve. Detailed socioeconomic data are therefore an essential input for the design of cost‐effective reserve networks.

Assembling a mutualism: ant symbionts locate their host plants by detecting volatile chemicals - D. P. Edwards; M. Hassall; W. J. Sutherland; D. W. Yu (Insectes Sociaux, 2006)

A Case Study on the Effects of Heterogeneous Soil Moisture on Mesoscale Boundary-Layer Structure in the Southern Great Plains, U.S.A. Part I: Simple Prognostic Model - Ankur R. Desai; Kenneth J. Davis; Christoph J. Senff; Syed Ismail; Edward V. Browell; David R. Stauffer; Brian P. Reen (Boundary-Layer Meteorology, 2006)

Two-locus genome-wide linkage scan for prostate cancer susceptibility genes with an interaction effect - Bao-Li Chang; Ethan M. Lange; Latchezar Dimitrov; Christopher J. Valis; Elizabeth M. Gillanders; Leslie A. Lange; Kathleen E. Wiley; Sarah D. Isaacs; Fredrik Wiklund; Agnes Baffoe-Bonnie; Carl D Langefeld; S. Lilly Zheng; et al. (Human Genetics, 2006)

Oracle-based optimization applied to climate model calibration - Cesar Beltran; N. R. Edwards; A. B. Haurie; J.-P. Vial; D. S. Zachary (Environmental Modeling & Assessment, 2006)

Transgenic Plants for Insect Pest Control: A Forward Looking Scientific Perspective - N. Ferry; M. G. Edwards; J. Gatehouse; T. Capell; P. Christou; A. M. R. Gatehouse (Transgenic Research, 2006)

Observation and Simulation of Root Reinforcement on Abandoned Mediterranean Slopes - L. P. H. van Beek; J. Wint; L. H. Cammeraat; J. P. Edwards (Plant and Soil, 2005)

Symmetry Solutions for Transient Solute Transport in Unsaturated Soils with Realistic Water Profile - R. J. Moitsheki; P. Broadbridge; M. P. Edwards (Transport in Porous Media, 2005)

Temporal discrimination of two passive movements in humans: a new psychophysical approach to assessing kinaesthesia - Michele Tinazzi; Clementina Stanzani; Mirta Fiorio; Nicola Smania; Giuseppe Moretto; Antonio Fiaschi; Mark J. Edwards; Kailash P. Bhatia; John C. Rothwell (Experimental Brain Research, 2005)

Development of baroreflex and endocrine responses to hypotensive stress in newborn foals and lambs - S. J. O’Connor; D. S. Gardner; J. C. Ousey; N. Holdstock; P. Rossdale; C. M. B. Edwards; A. L. Fowden; D. A. Giussani (Pflügers Archiv - European Journal of Physiology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Construction of a Festuca pratensis BAC library for map-based cloning in Festulolium substitution lines - Iain S. Donnison; Donal M. O’Sullivan; Ann Thomas; Peter Canter; Beverley Moore; Ian Armstead; Howard Thomas; Keith J. Edwards; Ian P. King (Theoretical and Applied Genetics, 2005)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

Threatened fishes of the world: Cyprinodon eximius Girard 1859 - Gary P. Garrett; Clark Hubbs; Robert J. Edwards (Environmental Biology of Fishes, 2005)

Refined histopathologic scoring system improves power todetect colitis QTL in mice - Andre Bleich; Michael Mähler; Claudia Most; Edward H. Leiter; Elisabeth Liebler–Tenorio; Charles O. Elson; Hans J. Hedrich; Brigitte Schlegelberger; John P. Sundberg (Mammalian Genome, 2004)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Mapping Ds insertions in barley using a sequence-based approach - L. D. Cooper; L. Marquez-Cedillo; J. Singh; A. K. Sturbaum; S. Zhang; V. Edwards; K. Johnson; A. Kleinhofs; S. Rangel; V. Carollo; P. Bregitzer; P. G. Lemaux; et al. (Molecular Genetics and Genomics, 2004)

Toxicological Evaluation and QSAR Modelling of Aromatic Amines to Chlorella vulgaris - T. I. Netzeva; J. C. Dearden; R. Edwards; A. D. P. Worgan; M. T. D. Cronin (Bulletin of Environmental Contamination and Toxicology, 2004)

Effects of Direct Ocean CO2 Injection on Deep-Sea Meiofauna - James P. Barry; Kurt R. Buck; Chris F. Lovera; Linda Kuhnz; Patrick J. Whaling; Edward T. Peltzer; Peter Walz; Peter G. Brewer (Journal of Oceanography, 2004)

A microsatellite marker based framework linkage map of Vitis vinifera L. - S. Riaz; G. S. Dangl; K. J. Edwards; C. P. Meredith (Theoretical and Applied Genetics, 2004)

Impact of soil warming and shading on colonization and community structure of arbuscular mycorrhizal fungi in roots of a native grassland community - Andreas Heinemeyer; Karyn P. Ridgway; Everard J. Edwards; David G. Benham; J. Peter W. Young; Alastair H. Fitter (Global Change Biology, 2004)
Arbuscular mycorrhizal (AM) fungi have a major influence on the structure, responses and below‐ground C allocation of plant communities. Our lack of understanding of the response of AM fungi to factors such as light and temperature is an obstacle to accurate prediction of the impact of global climate change on ecosystem functioning. In order to investigate this response, we divided a grassland site into 24 plots, each either unshaded or partly shaded with soil either unheated or heated by 3°C at 2 cm depth. In both short‐term studies in spring and autumn, and in a 1‐year‐long study, we measured root length colonization (L R C) by AM and non‐AM fungi. For selected root samples, DNA sequences were amplified by PCR with fungal‐specific primers for part of the small sub‐unit (SSU) rRNA gene. In spring, the total L R C increased over 6 weeks from 12% to 25%. Shading significantly reduced AM but increased non‐AM fungal colonization, while soil warming had no effect. In the year‐long study, colonization by AM fungi peaked in summer, whereas non‐AM colonization peaked in autumn, when there was an additive effect of shading and soil warming that reduced AM but increased non‐AM fungi. Stepwise regression revealed that light received within the 7 days prior to sampling was the most significant factor in determining AM L R C and that mean temperature was the most important influence on non‐AM L R C. Loglinear analysis confirmed that there were no seasonal or treatment effects on the host plant community. Ten AM fungal sequence types were identified that clustered into two families of the Glomales, Glomaceae and Gigasporaceae. Three other sequence types were of non‐AM fungi, all Ascomycotina. AM sequence types showed seasonal variation and shading impacts: loglinear regression analysis revealed changes in the AM fungal community with time, and a reduction of one Glomus sp. under shade, which corresponded to a decrease in the abundance of Trifolium repens. We suggest that further research investigating any impacts of climate change on ecosystem functioning must not only incorporate their natural AM fungal communities but should also focus on niche separation and community dynamics of AM fungi.

Immunization with a vaccine that combines the expression of MUC1 and B7 co-stimulatory molecules prolongs the survival of mice and delays the appearance of mouse mammary tumors - Vitaly Vasilevko; Anahit Ghochikyan; Nadya Sadzikava; Irina Petrushina; Mike Tran; Edward P. Cohen; Patrick J. Kesslak; David H. Cribbs; Garth L. Nicolson; Michael G. Agadjanyan (Clinical & Experimental Metastasis, 2003)

Precision of Dialysis (Peeper) Sampling of Cadmium in Marine Sediment Interstitial Water - J. R. Serbst; R. M. Burgess; A. Kuhn; P. A. Edwards; M. G. Cantwell; M. C. Pelletier; W. J. Berry (Archives of Environmental Contamination and Toxicology, 2003)

Threatened Fishes of the World: Gambusia heterochir Hubbs, 1957 (Poeciliidae) - Clark Hubbs; Robert J. Edwards; Gary P. Garrett (Environmental Biology of Fishes, 2002)

Threatened Fishes of the World: Dionda diaboli Hubbs & Brown, 1956 (Cyprinidae) - Gary P. Garrett; Clark Hubbs; Robert J. Edwards (Environmental Biology of Fishes, 2002)

Threatened Fishes of the World: Gambusia georgei Hubbs & Peden, 1969 (Poeciliidae) - Robert J. Edwards; Clark Hubbs; Gary P. Garrett (Environmental Biology of Fishes, 2002)

Threatened Fishes of the World: Cyprinodon pecosensis Echelle & Echelle, 1978 (Cyprinodontidae) - Gary P. Garrett; Clark Hubbs; Robert J. Edwards (Environmental Biology of Fishes, 2002)

Threatened Fishes of the World: Cyprinodon elegans Baird & Girard, 1853 (Cyprinodontidae) - Gary P. Garrett; Clark Hubbs; Robert J. Edwards (Environmental Biology of Fishes, 2002)

Nitrogen fixation and nitrogen isotope abundances in zooplankton of the oligotrophic North Atlantic - Joseph P. Montoya; Edward J. Carpenter; Douglas G. Capone (Limnology and Oceanography, 2002)
Deep‐water nitrate is a major reservoir of oceanic combined nitrogen and has long been considered to be the major source of new nitrogen supporting primary production in the oligotrophic ocean. 15 N: 14 N ratios in plankton provide an integrative record of the nitrogen cycle processes at work in the ocean, and near‐surface organic matter in oligotrophic waters like the Sargasso Sea is characterized by an unusually low 15 N content relative to average deep‐water nitrate. Herein we show that the low dΔ 15 N of suspended particles and zooplankton from the tropical North Atlantic cannot arise through isotopic fractionation associated with nutrient uptake and food web processes but are instead consistent with a significant input of new nitrogen to the upper water column by N 2 fixation. These results provide direct, integrative evidence that N 2 fixation makes a major contribution to the nitrogen budget of the oligotrophic North Atlantic Ocean.

Threatened Fishes of the World: Gambusia gaigei Hubbs, 1929 (Poeciliidae) - Clark Hubbs; Robert J. Edwards; Gary P. Garrett (Environmental Biology of Fishes, 2002)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Threatened Fishes of the World: Cyprinodon bovinus Baird & Girard, 1853 (Cyprinodontidae) - Gary P. Garrett; Clark Hubbs; Robert J. Edwards (Environmental Biology of Fishes, 2002)

Threatened Fishes of the World: Gambusia nobilis Baird & Girard, 1853 (Poeciliidae) - Clark Hubbs; Robert J. Edwards; Gary P. Garrett (Environmental Biology of Fishes, 2002)

Threatened Fishes of the World: Gambusia amistadensis Peden, 1973 (Poeciliidae) - Robert J. Edwards; Clark Hubbs; Gary P. Garrett (Environmental Biology of Fishes, 2002)

Conservation and status of the fish communities inhabiting the Río Conchos basin and middle Rio Grande, México and U.S.A. - Robert J. Edwards; Gary P. Garrett; Edie Marsh-Matthews (Reviews in Fish Biology and Fisheries, 2002)

Hybrid cluster proteins (HCPs) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at 1.25 Å resolution using synchrotron radiation - Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Serena J. Cooper; Ricardo Coelho; Ming Y. Liu; António V. Xavier; Jean LeGall; Susan Bailey; David C. Garner; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2002)

Development of Stem-base Pathogens on Different Cultivars of Winter Wheat Determined by Quantitative PCR - P. Nicholson; A.S. Turner; S.G. Edwards; G.L. Bateman; L.W. Morgan; D.W. Parry; J. Marshall; M. Nuttall (European Journal of Plant Pathology, 2002)

The C1 locus in maize (Zea mays L.): effect on gene expression - J. Edwards; D. Stoltzfus; P. A. Peterson (Theoretical and Applied Genetics, 2001)

Multiple Ligand and Cell-Dependent States of Lateral Mobility of Plasmalemmal G Protein-Coupled Cholecystokinin Receptors - Belinda F. Roettger; Edward H. Hellen; Thomas P. Burghardt; Laurence J. Miller (Journal of Fluorescence, 2001)

Availability of medicines in the European Union: results from the EURO-Medicines project - Folino-Gallo P.; Walley T.; Frolich J.; Carvajal A.; Edwards I. (European Journal of Clinical Pharmacology, 2001)

A maize bacterial artificial chromosome (BAC) library from the European flint inbred line F2 - D. M. O’Sullivan; P. J. Ripoll; M. Rodgers; K. J. Edwards (Theoretical and Applied Genetics, 2001)

Potassium nutrition effects on seed alkaloid concentrations, yield and mineral content of lupins (Lupinus angustifolius) - P. Gremigni; M. T. F. Wong; N. K. Edwards; D. Harris; J. Hamblin (Plant and Soil, 2001)

Unprecedented bleaching-induced mortality in Porites spp. at Rangiroa Atoll, French Polynesia - Mumby P.; Chisholm J.; Edwards A.; Clark C.; Roark E.; Andrefouet S.; Jaubert J. (Marine Biology, 2001)

Decaying Scalars Emitted By A Forest Canopy: A Numerical Study - Edward G. Patton; Kenneth J. Davis; Mary C. Barth; Peter P. Sullivan (Boundary-Layer Meteorology, 2001)

Simple sequence repeat (SSR) markers survey of the cassava (Manihot esculenta Crantz) genome: towards an SSR-based molecular genetic map of cassava - R. E. C. Mba; P. Stephenson; K. Edwards; S. Melzer; J. Nkumbira; U. Gullberg; K. Apel; M. Gale; J. Tohme; M. Fregene (Theoretical and Applied Genetics, 2001)

Reproductive performance of a harpactorine reduviid Rhynocoris fuscipes (Fabricius) (Heteroptera: Reduviidae) on three lepidopteran insect pests - P. J. Edward George (International Journal of Tropical Insect Science, 2000)

Microsatellites for Barren Brome ( Anisantha sterilis ) - J. M. Green; K. J. Edwards; S. L. Usher; J. H. A. Barker; E. J. P. Marshall; R. J. Froud‐Williams; A. Karp (Molecular Ecology, 2000)

Intact negative patterning in rats with fornix or combined perirhinal and postrhinal cortex lesions - Timothy J. Bussey; Rebecca Dias; Edward S. Redhead; John M. Pearce; Janice L. Muir; John P. Aggleton (Experimental Brain Research, 2000)

Effects of pH and Dose on Nasal Absorption of Scopolamine Hydrobromide in Human Subjects - Shamim Ahmed; Anthony P. Sileno; Jorge C. deMeireles; Ramneik Dua; Harish K. Pimplaskar; Wei J. Xia; John Marinaro; Edward Langenback; Frank J. Matos; Lakshmi Putcha; Vincent D. Romeo; Charan R. Behl (Pharmaceutical Research, 2000)

Characterisation and analysis of microsatellite loci in a mangrove species, Avicennia marina (Forsk.) Vierh. (Avicenniaceae) - T. L. Maguire; K. J. Edwards; P. Saenger; R. Henry (Theoretical and Applied Genetics, 2000)

Geochemistry and tectonic significance of peridotites from the South Sandwich arc-basin system, South Atlantic - J. A. Pearce; P. F. Barker; S. J. Edwards; I. J. Parkinson; P. T. Leat (Contributions to Mineralogy and Petrology, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

A prospective study of plasma ascorbic acid concentrations and breast cancer (United States) - Kana Wu; Kathy J. Helzlsouer; Anthony J. Alberg; George W. Comstock; Edward P. Norkus; Sandra C. Hoffman (Cancer Causes & Control, 2000)

Effects of supplemental α-tocopherol and β-carotene on colorectal cancer: results from a controlled trial (Finland) - Demetrius Albanes; Nea Malila; Philip R. Taylor; Jussi K. Huttunen; Jarmo Virtamo; Brenda K. Edwards; Matti Rautalahti; Anne M. Hartman; Michael J. Barrett; Pirjo Pietinen; Terryl J. Hartman; Pentti Sipponen; et al. (Cancer Causes & Control, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Preface - Kevin J. Edwards; Jon P. Sadler (Journal of Quaternary Science, 1999)

Introduction: striving for an environment-human consensus - Kevin J. Edwards; Jon P. Sadler (Journal of Quaternary Science, 1999)

Dimerisation of maize glutathione transferases in recombinant bacteria - David P. Dixon; David J. Cole; Robert Edwards (Plant Molecular Biology, 1999)

A microsatellite marker associated with a QTL for grain protein content on chromosome arm 2DL of bread wheat - M. Prasad; R. K. Varshney; A. Kumar; H. S. Balyan; P. C. Sharma; K. J. Edwards; H-Singh; H. S. Dhaliwal; J. K. Roy; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Identification of a microsatellite on chromosomes 6B and a STS on 7D of bread wheat showing an association with preharvest sprouting tolerance - J. K. Roy; M. Prasad; R. K. Varshney; H. S. Balyan; T. K. Blake; H. S. Dhaliwal; H-Singh; K. J. Edwards; P. K. Gupta (Theoretical and Applied Genetics, 1999)

Abundance and polymorphism of microsatellite markers in the tea tree (Melaleuca alternifolia, Myrtaceae) - M. Rossetto; A. McLauchlan; F. C. L. Harriss; R. J. Henry; P. R. Baverstock; L. S. Lee; T. L. Maguire; K. J. Edwards (Theoretical and Applied Genetics, 1999)

Contribution of NMDA and non-NMDA receptors to synaptic transmission from the brachium of the inferior colliculus to the medial subdivision of the medial geniculate nucleus in the rabbit - Tim J. Webber; Edward J. Green; Ray W. Winters; Neil Schneiderman; P. M. McCabe (Experimental Brain Research, 1999)

Errata - Kell Kristiansen; Lars P. Christensen; Yurong Chen; Edward O. Kenaschuk; J. Doug Procunier (Euphytica, 1998)

No genetic variation detected within isolated relict populations of Saxifraga cernua in the Alps using RAPD markers - M. R. BAUERT; M. KÄLIN; M. BALTISBERGER; P. J. EDWARDS (Molecular Ecology, 1998)
Genetic variation in seven relict populations of Saxifraga cernua from three regions of the Alps was investigated using RAPD (random amplified polymorphic DNA) markers. No variation, either within the populations or within the regions, could be demonstrated. Nevertheless, each alpine region was characterized by a unique RAPD phenotype. Absence of genetic variation in these relict populations is attributed to population bottlenecks and founder effects during or following the ice ages. Contrasting hypotheses about the history of these populations, either as survivors of the glacial period or as products of postglacial immigration, are discussed in the light of the data presented.

CO2 and O2 dependence of PS II activity in C4 plants having genetically produced deficiencies in the C3 or C4 cycle - João P. Maroco; Maurice S. B. Ku; Robert T. Furbank; Peter J. Lea; Richard C. Leegood; Gerald E. Edwards (Photosynthesis Research, 1998)

Regulating exercise intensity using ratings of perceived exertion during arm and leg ergometry - Jie Kang; Edward C. Chaloupka; M. Alysia Mastrangelo; M. Scott Donnelly; William P. Martz; Robert J. Robertson (European Journal of Applied Physiology, 1998)

Effects of delivery rate and non-contingent infusion of cocaine on cocaine self-administration in rhesus monkeys - L. V. Panlilio; Steven R. Goldberg; Joanne P. Gilman; Rebecca Jufer; Edward J. Cone; Charles W. Schindler (Psychopharmacology, 1998)

Correlation between Waardenburg syndrome phenotype and genotype in a population of individuals with identified PAX3 mutations - Anita L. DeStefano; L. Adrienne Cupples; Kathleen S. Arnos; J. H. Jr. Asher; Clinton T. Baldwin; Susan Blanton; Melisa L. Carey; Elias O. da Silva; T. B. Friedman; Jacquie Greenberg; Anil K. Lalwani; Aubrey Milunsky; et al. (Human Genetics, 1998)

A cluster of stearoyl CoA desaturase genes, Scd1 and Scd2, on mouse Chromosome 19 - D. E. Tabor; Y. -R. Xia; M. Mehrabian; P. A. Edwards; A. J. Lusis (Mammalian Genome, 1998)

Digital analysis of multispectral airborne imagery of coral reefs - P. J. Mumby; E. P. Green; C. D. Clark; A. J. Edwards (Coral Reefs, 1998)

Tumor cell contact mediated transcriptional activation of the fibroblast matrix metalloproteinase-9 gene: involvement of multiple transcription factors including Ets and an alternating purine-pyrimidine repeat - Bruce P. Himelstein; Edward J. Lee; Hiroshi Sato; Motoharu Seiki; Ruth J. Muschel (Clinical & Experimental Metastasis, 1998)

Purification, regulation and cloning of a glutathione transferase (GST) from maize resembling the auxin-inducible type-III GSTs - David P. Dixon; David J. Cole; Robert Edwards (Plant Molecular Biology, 1998)

Body size and sexual size dimorphism in calanoid copepods - Edward J. Maly; Mary P. Maly (Hydrobiologia, 1998)

Coral reef habitat mapping: how much detail can remote sensing provide? - P. J. Mumby; E. P. Green; A. J. Edwards; C. D. Clark (Marine Biology, 1997)

Withdrawal reactions with selective serotonin re-uptake inhibitors as reported to the WHO system - M. M. S. Stahl; M. Lindquist; M. Pettersson; I. R. Edwards; J. H. Sanderson; N. F. A. Taylor; A. P. Fletcher; J. S. Schou (European Journal of Clinical Pharmacology, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Minimum sample sizes for identifying chromosomal fragile sites from individuals: Monte Carlo estimation - I. F. Greenbaum; J. K. Fulton; Edward D. White; P. Fred Dahm (Human Genetics, 1997)

Predation, competition, and co-occurrences of Boeckella and Calamoecia (Copepoda: Calanoida) in Western Australia - Edward J. Maly; Mary P. Maly (Hydrobiologia, 1997)

The comparative biology of the pupal endoparasitoidPsychophagus omnivorus (Hym.:Pteromalidae) on three candidate lepidopteran hosts - H. J. Mosson; G. C. Marris; J. P. Edwards (BioControl, 1997)

Atmospheric Effects of the Emerging Mainland Chinese Transportation System at and Beyond the Regional Scale - SCOTT ELLIOTT; MEI SHEN; DONALD R. BLAKE; RONG LU; ARMISTEAD G. RUSSELL; C. Y. J. KAO; GERALD E. STREIT; XUE PENG ZHAO; EDWARD IAIN McCREARY; F. SHERWOOD ROWLAND; MICHAEL J. BROWN; RICHARD P. TURCO (Journal of Atmospheric Chemistry, 1997)

Diet and feeding ecology of the diving petrels Pelecanoides georgicus and P. urinatrix at South Georgia - K. Reid; J. P. Croxall; T. M. Edwards; H. J. Hill; P. A. Prince (Polar Biology, 1997)

Dislodgeable residues of ethion in Florida citrus and relationships to weather variables - H. N. Nigg; J. C. Allen; R. F. Brooks; G. J. Edwards; N. P. Thompson; Roy W. King; A. H. Blagg (Archives of Environmental Contamination and Toxicology, 1977)

Activity of phenol oxidases at the puparium formation stage in development of nineteen lozenge mutants of Drosophila melanogaster - E. Edward Peeples; Ann Geisler; Carol J. Whitcraft; Clarence P. Oliver (Biochemical Genetics, 1969)

Three new Arizona types isolated from normal reptiles - Carolyn H. Ramsey; J. G. Heyl; P. R. Edwards (Antonie van Leeuwenhoek, 1960)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

Potato flakes. A new form of dehydrated mashed potatoes - Miles J. Willard; James Cording; R. K. Eskew; P. W. Edwards; John F. Sullivan (American Journal of Potato Research, 1956)

Four newSalmonella serotypes isolated in curacao - P. R. Edwards; F. J. Rutten; Alma C. McWhorter (Antonie van Leeuwenhoek, 1955)